Phytochemical Profiling and Antibacterial Potential of Propolis Extract and Green Synthesis of Silver Nanoparticles: An Experimental and Computational Approach - Ateeq Ur Rahman; Mohammad Attaullah; Aqsa Gul; Robi Bibi; Bashir Ahmad; Aziz Ullah; Abdulwahed Fahad Alrefaei; Faheem Anwar; Sajid Ali (Journal of Pharmaceutical Innovation, 2027)

Dry ice-driven CO 2 sequestration in cementitious materials: effects on hydration, microstructure, and mechanical performance - Shamsad Ahmad; Khaled M. Kharma; Rida Assaggaf; Mohammed A. Al-Osta; Ali H. Algozeeb; Wala A. Algozeeb; Mohammed A. Al-Huri; Md. Abdul Aziz (European Journal of Environmental and Civil Engineering, 2026)

Nostoc sp.-mediated silver nanoparticles: biosynthesis, characterization, antibacterial activity, and cytocompatibility assessment - Rebwar Khdir Shekha; Fairuz H. Abdullah Tawgozy; Sayran Abdulrahman Qadir; Abdullah Hamad Aziz; Rebwar Muhammad Hamasalih; Roza Talaat Yaseen; Mohsin Ali Ahmad; Zirak Faqe Ahmed Abdulrahman (Archives of Microbiology, 2026)

SLCO1B1 and MTRR gene variants in pediatric acute lymphoblastic leukemia: a study on Egyptian children - Ali Nabeel Mahdi; Afaf M. Elsaid; Maha Abdelmoneim Mohammed; Mai M. Madkour; A. F. Abdel-Aziz (Molecular Biology Reports, 2026)

Mite pests of date palm (Phoenix dactylifera L.) and their management: a review with emphasis on Oligonychus afrasiaticus (McGregor) - Ali Omari Alaoui; Abdelmalek Boutaleb Joutei; Moulay Chrif Smaili; Nourredine Chtaina; Mohammed Aziz Elhoumaizi (Phytoparasitica, 2026)

Emerging advanced technologies: Modulation of sensory properties in milk and whey systems – A review - Waris Aziz; Khawaja Muhammad Ali Tayyab; Tahir Mahmood Qureshi; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Trends in Food Science & Technology, 2026)

Recent advances in nZVI@MOF composites for Cr(VI) removal: A comprehensive review - Safina Zafar; Shumaila Bibi; Mohamed H. Helal; Haider Ali; Guilherme Luiz Dotto; Zeinhom M. El-Bahy; Muhammad Ahmad Wattoo; Aziz ur Rehman (Journal of Environmental Chemical Engineering, 2026)

Next-generation Ti3C2 MXenes quantum dots modified g-C3N4 nanosheets photocatalysts for enhanced CO2 reduction to green fuels and chemicals - Md Mohshin Ali; Azrina Abd Aziz; Md. Arif Hossen; Suryanti Awang; Mohamed Kheireddine Aroua (Journal of Environmental Chemical Engineering, 2026)

Germination-driven biochemical remodeling of cereals and pseudocereals: Impacts on nutrient bioaccessibility, phytochemical enrichment, and functional food potential - Djilali Benabdelmoumene; Muhammad Waqar; Abderahman Shawky; Omnia Darwish Askar; Wasim S.M. Qadi; Said Dahmouni; Mariam Gamaleldin; Faidruz Azura Jam; Ahmed Mediani; Hamizah Shahirah Hamezah; Habsah Aziz; Sajad Ali; et al. (Food Chemistry, 2026)

Rethinking falling number in climate-volatile cereals: from a single quality threshold to diagnostic phenotyping of alpha-amylase, sprouting and grain functionality - Aziz Ullah; Atif Ali Khan Khalil (Cereal Research Communications, 2026)

Life cycle assessment of the Mekong Delta rice supply chain: emission inventory and mitigation pathways toward food security synergies - Van Tinh Thai; Julia Checco; Jaquie Mitchell; Md. Ali Akber; Ammar Abdul Aziz (Journal of Cleaner Production, 2026)

Paleoenvironmental conditions across the Jurassic–Cretaceous boundary from northern Arabia: Facies analysis, mineralogical and geochemical implications - Alaa M. Al-Wazan; Ali I. Al-Juboury; Nisreen M. Aziz; Ahmed H. Al-Obeidi; Nasir Alarifi; Harry Rowe; Giovanni Zanoni; Justyna Kowal-Kasprzyk; Anna Waśkowska; Nagham Omar; Fathy Abdalla (Journal of African Earth Sciences, 2026)

Development of food 3D printing mixing system: A semi-batch process mixing device suitable for aging friendly product - Lin Lin; Yixin Xue; Xiaochen Chen; Tariq Aziz; Rania Ali El Hadi Mohamed; Nawal Al-Hoshani; Fahad Al-Asmari; Haiying Cui (Innovative Food Science & Emerging Technologies, 2026)

Gelatinization and Retrogradation of isolated potato starch and potato flour: Effect of time and storage temperature assessed by LF-NMR - Sara Aghajanzadeh; Aziz Belarroud; Ali Asghari; Seddik Khalloufi (Food Chemistry, 2026)

Type 2 Diabetes-Induced Molecular and Functional Impairment of Adipose Tissue-Derived Mesenchymal Stromal Cells (ASCs) and Interferon Gamma Priming for Enhanced Diabetic ASC-Based Therapy - Alaa Zeinhom; Ammar Y. Mohamed; Nahla N. Abdel-Aziz; Mostafa Sayed Diab; Amir M. H. Salem; Noha N. Yassen; Eman E. A. Mohammed; Amal M. Mohamed; Ola M. Eid; Shymaa H. Hussein; Marwa Farid; Engy K. Tharwat; et al. (Stem Cell Reviews and Reports, 2026)

Effect of long-term use of very low-carbohydrate Ketogenic diet on the thyroid gland and adipose tissue of adult male albino rats (biochemical and histological study) - Randa Ahmed Ibrahim; Nehal Mohammed Elwaddah; Neven Makram Aziz; Jermeen Emad Yousef; Seham Abd El-Raouf Abd El-Aleem; Entesar Ali Saber (Journal of Molecular Histology, 2026)

Short-Term Soil Health Responses to Biochar and Irrigation in a Sandy Loam Soil - Md Ali Haider; Jim J. Wang; Syam K. Dodla; Krizzia Guardado; Aziz Ahmed; Changyoon Jeong; Lewis A. Gaston (Journal of Soil Science and Plant Nutrition, 2026)
This study was conducted to determine how irrigation alters the effects of biochar on soil health parameters in a coarse texture soil for two consecutive growing seasons. Surface soil (0–15 cm) samples from a split-plot randomized block design (main plots, unirrigated and irrigated; subplots, 0 and 11.2 Mg ha − 1 biochar) taken after soybean ( Glycine max ) harvest in 2022 and 2023 were analyzed for electrical conductivity, pH, labile and total C, inorganic and total N, respiration rate, activities of four extracellular enzymes, and phospholipid fatty acid profiles. Yield was also measured. Neither biochar nor irrigation increased yield. Biochar increased pH and β-glucosidase activity but decreased phosphatase activity. Irrigation reduced organic C, respiration and activities of all enzymes except arylsulfatase. Principle component analysis showed that parameters related to organic C turnover were important without irrigation. Structural equation modeling for respiration rate found small positive effects of phosphatase activity and labile C with irrigation ( P < 0.10), but large positive effect of phosphatase without ( P < 0.01). An interrelationship of other enzymes and microbial biomass was important to respiration without irrigation, though not with irrigation. The effect of irrigation on soil health parameters in a coarse texture soil for two growing seasons was greater than the effect of biochar.

Development of Novel Braided Fibreglass (FG) Rock Bolts with Robust Shear Strength Properties-Part II: Large-Scale Mechanical Performance Evaluation - Shima Entezam; Behshad Jodeiri Shokri; Hadi Nourizadeh; Alireza Entezam; Mazhar Peerzadeh; Kevin McDougall; Warna Karunasena; Naj Aziz; Ali Mirzaghorbanali (Rock Mechanics and Rock Engineering, 2026)
The limited shear capacity and brittle failure of conventional pultruded glass fibre-reinforced polymer (GFRP) rock bolts continue to restrict their application, despite advantages such as corrosion resistance and cuttability. To address this, our earlier study (Paper 1) developed braidtrusion-manufactured prototypes of GFRP rock bolts infused with graphene–epoxy matrices and identified two optimised designs, RE6 (22 mm) and RE7 (35 mm), that demonstrated promising improvements in shear capacities in guillotine shear tests. While these laboratory-scale findings confirmed the potential of the new manufacturing process, they did not capture the full spectrum of loading conditions experienced underground. This paper presents the second stage of the research programme, focussing on the large-scale mechanical evaluation of the RE6 and RE7 prototypes. A comprehensive experimental scheme was undertaken, including concrete-embedded double-shear tests, double-embedment pull-out tests, axial tensile tests, and torsion tests, designed to replicate realistic service conditions. The results demonstrated that shear capacity was strongly influenced by diameter: RE7 achieved a peak double-shear load of 266.9 kN compared with 185.5 kN for RE6, both showing stable post-peak behaviour. In axial pull-out tests, peak capacities of 414.6 kN (RE7) and 309.7 kN (RE6) were recorded, with failure governed by progressive debonding rather than abrupt rupture. Double-embedment tensile tests returned high peak loads with controlled post-peak softening rather than brittle failure, RE6 reached 330.5 kN at 15.1 mm and RE7 452.7 kN at 19.4 mm, with debonding governed by rib–grout interaction and no tendon damage observed. Torsion tests revealed maximum torques of 1.02 kN·m for RE7 and 0.50 kN·m for RE6, with no damage observed. By linking the manufacturing innovations reported in Paper 1 with systematic large-scale validation, this study established a modified manufacturing process of fibreglass rock bolts as high-capacity, energy-absorbing alternatives to steel rock bolts, capable of addressing the shear limitations that have historically constrained GFRP applications in mining and civil ground support.

Injectable bioactive hydrogels as pharmacological drug delivery platforms for post-myocardial infarction cardiac repair: therapeutic cargo engineering, stimuli-responsive release mechanisms, and translational perspectives - Amr Ali Mohamed Abdelgawwad El-Sehrawy; Safa Alkhayyat; Mirza R. Baig; Aziz Kubaev; Tushar B. Gajjar; Malathi Hanumanthayya; Laxmidhar Maharana; Irwanjot Kaur; Aseel Smerat; Narges Fereydouni (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Influence of pyrolysis temperature on pineapple peel derived-porous biochar for electrochemical detection of bisphenol A - Mohamad Aizad Mohd Mokhtar; Azila Abdul-Aziz; Dayang Norulfairuz Abang Zaidel; Roshafima Rasit Ali; Seiya Tsujimura; Zhongfang Lei (Biomass and Bioenergy, 2026)

Assessment of Fine Particulate Matter (PM2.5) Induced Cyto-Genotoxicity in a Highly Polluted Urban Environment: Evidence from Lahore, Pakistan - Meerub Shazad; Muhammad Muddassir Ali; Syed Aziz ur Rehman; Maryam Javed; Jabir Hussain Syed; Asad Ullah (Water, Air, & Soil Pollution, 2026)

Functional textile dyeing with microbial pigments from Serratia sp. EIKU25 using agro-waste derived bio-mordants within a circular economy framework - Taniya Roy; Shashwata Mainak; Atif Aziz Chowdhury; Sayantani Paul; Nilendu Basak; Anindita Bhattacharjee; Sk. Imran Ali; Arunima Biswas; Ekramul Islam (Bioresource Technology Reports, 2026)

Application of discriminant analysis, classification and regression tree (CART) methods to some morphometric data for the classification of Kouri cattle in the Lake Chad Province, Republic of Chad - Mahamat Ali Amine Ouchar; Djomtchaigue Bamare Herbert; Mahamat Tahir Youssouf; Baizina Mama; Abdelkerim Abdoulaye Seıd; Abdel-Aziz Arada Izzedıne; Özcan Şahin; İsmail Keskin; İbrahim Aytekin (Tropical Animal Health and Production, 2026)

Partial Root-Zone Drying and Regulated Deficit Irrigation Effects on Potato Yield, Quality, Water Productivity, and Net Profit under Surface vs. Subsurface Drip Irrigation - Mohamed H. Abd El-Wahed; Mahmoud M. Ali; Ahmed A. Abdel-Aziz; Yahia A. M. Ibrahim (Potato Research, 2026)

Hormonal Coordination of Fruit Development and Ripening: An Integrated Molecular Perspective - Sabir Iqbal; Komal Tariq; Shahzad Ali; Essam Elatafi; Rana Badar Aziz; Basma Elhendawy; Jinggui Fang (Applied Fruit Science, 2026)

Integrative 16S rRNA characterization, pan-genome, and immunoinformatics approaches for the design of a multi-epitope vaccine against Bacillus cereus, a foodborne pathogen - Muhammad Asim; Muhammad Naveed; Tariq Aziz; Muhammad Toheed; Hafiz Muzzammel Rehman; Nawal Al-Hoshani; Rania Ali El Hadi Mohamed; Maher S. Alwethaynani; Areej A Alhhazmi; Manal F. Elkhadragy (World Journal of Microbiology and Biotechnology, 2026)

Lead and cadmium contamination in soils: impacts and phytoremediation strategies using ornamental plants, nanoparticles, and organic growth regulators - Sumbal Ammara; Muhammad Tariq Rafiq; Basharat Ali; Rukhsanda Aziz; Maria Aziz (Environmental Monitoring and Assessment, 2026)

Upcycling marine food waste into biodegradable food packaging: A sustainable approach toward zero-waste society and biocircular economy - Kasun Kumara Dissanayake; Tonni Agustiono Kurniawan; Prakash Kumar Sarangi; G. Abdulkareem AlSultan; Hui Hwang Goh; Hin Yong Wong; Choo Wou Onn; Mohamed Tharikulislam; Faisal Aziz; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Imran Ali; et al. (Biomass and Bioenergy, 2026)

Investigating Climate Extremes over Yangtze River Delta, China: A Comprehensive Spatiotemporal Analysis and Insights - Ali Salem Al-Sakkaf; Mohammed Magdy Hamed; Abdulhaleem H. Labban; Ali Almahri; Adeel Ahmad; Abdoul Aziz Saidou Chaibou; Yasser M. Khalil; Jiahua Zhang; Fengmei Yao; Shamsuddin Shahid; Mohanned Abduljabbar Hael (Pure and Applied Geophysics, 2026)

Nitrogen fertilization shapes rhizosphere microbiome to boost peanut yield: A two-year field study - Xiangjun Kong; Peipei Jia; Lijie Li; Ali Muhammad; Rui Wang; Aziz Khan; Jaya Nepal; Fei Li; Zhiyong Zhang (Applied Soil Ecology, 2026)

Transdermal self-assembled Xanthine/hybrid needle nanofibers for management of abdominal obesity via phosphodiesterase 4B suppression - Soad A. Mohamed; Mohamed A. Abdelgawad; Rania Alaeddin; Mohamed Hisham; Entesar Ali Saber; Abdelaziz A. Nayl; Samy Selim; Mohamed Abdel-aziz; Alaa M. Hayallah; Mahmoud Elrehany; Eman Maher Zahran (Molecular Diversity, 2026)

Assessment of urban and peri-urban grazing practices from herders and local community perspective in the semiarid region of Pakistan - Muhammad Farooq Azhar; Ghulam Yasin; Asghar Ali; Abida Aziz; Ghulam Yasin; Daniyal Hussain; Ehsan Ali (Environmental Monitoring and Assessment, 2026)

Synergistic effects of zinc and reduced glutathione application on growth, yield, gas exchange attributes, water relations, and metabolite profiles in Zea mays (L.) plants under water deficit irrigation - Farah Saeed; Qasim Ali; Suliman Mohammed Suliman Alghanem; Abida Kausar; Rashida Perveen; Haifa Abdul Aziz Sakit Alhaithloul; Muhammad Rizwan (South African Journal of Botany, 2026)

Individual and combined decontamination effect of aqueous ozone and plant extracts on fungi and aflatoxins in brown rice - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Muhammad Arif Shahzad; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos A.F. Oliveira (Food Control, 2026)

Bacterial Metabolite-Derived NDM-1 Inhibitors: A Computational Strategy to Overcome β-Lactam Resistance - Bader S. Alotaibi; Farhat Shabbir; Muhammad Umer Khan; Iqra Ahmad; Hira Khalid; Shahid Aziz; Abid Ali; Sonia Younas; Hanna Dib; Khaled Fahmi Fawy; Umar Nishan; Mohibullah Shah (Probiotics and Antimicrobial Proteins, 2026)

Protective role of agomelatine via modulation of TLR4/NF-κB: NLRP3/IL-1β signaling pathways in testosterone-induced benign prostatic hyperplasia in rats - Asmaa Mohamed Abdel-Aziz; Sara M. Ahmed; Walaa Yehia Abdelzaher; Nada Amgad Mohamed; Alyaa E. Abdelkader; Rasha Fouad Ahmed; Asmaa Mohamed Mahmoud Ali; Al Shimaa Mahmoud Kotb; Alyaa Abdelfattah Abdelmonaem (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Benign prostatic hyperplasia (BPH) is a prevalent urological disorder in aging men, frequently linked to hormonal fluctuations. Agomelatine (AGO), a melatonergic receptor agonist and serotonin 2C antagonist, has demonstrated anti-inflammatory and antioxidant properties. This study aimed to explore the potential of AGO in mitigating BPH induced by testosterone propionate (TP) in rats. Male rats received TP (5 mg/kg/day, subcutaneously) to induce BPH and were pretreated with AGO (80 mg/kg/day) for 28 days. AGO inhibited the rise in prostate index, serum prostate-specific antigen (PSA), and testosterone levels compared to the BPH-only group. Histological analysis revealed that AGO significantly improved the pathological alterations in prostate tissue architecture when compared to BPH-only group. Furthermore, AGO notably reduced oxidative stress induced by TP, evidenced by a decrease in lipid peroxidation and preserved levels of reduced glutathione. This reduction in oxidative stress led to a decrease in pro-inflammatory cytokines in the prostate, such as Toll-like receptor 4 (TLR4) and interleukin-1 beta (IL-1β). Additionally, AGO caused a marked decrease in of NLRP3 inflammasome and vascular endothelial growth factor-A (VEGF-A) protein expressions. When compared to the BPH group, AGO’s effects also included a reduction in the immunoexpression of nuclear factor kappa B (NF-κB) and myeloid differentiation primary response 88 (MyD88) proteins. The findings from this study provide new evidence that AGO can alleviate testosterone-induced BPH in rats, likely through the inhibition of the TLR4/NFκB and NLRP3/IL-1β signaling pathways. These results suggest that AGO could be a promising therapeutic option for managing BPH. Graphical Abstract

Biochar and Montmorillonite in Combination Improved the Plant growth, physiology, Yield and Decreased Lead (Pb) Uptake in Wheat (Triticum aestivum L.) Under Pb Stress - Zaffar Malik; Suliman Mohammed Suliman Alghanem; Nasir Masood; Hina Rizvi; Muhammad Waseem; Ahmad Ali; Haifa Abdul Aziz Sakit Alhaithloul; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2026)

Effect of Biofertilizer and nurse plants on mycorrhizal status, soil fertility, and date palm productivity under organic farming system - Ou-Zine Mohamed; Symanczik Sarah; El Kinany Said; Aziz Larbi; Fagroud Mustapha; Abidar Ali; Mäder Paul; Achbani El Hassan; Haggoud Abdellatif; El Hilali Rania; Abdellaoui Mustapha; Bouamri Rachid (Organic Agriculture, 2026)

Evaluation of leaf extracts of Moringa oleifera Lam. On testosterone enanthate-induced polycystic ovary syndrome (PCOS) in mice - Shakeela Khalid; Muhammad Arshad; Farzana Siddque; Muhammad Sajid Arshad; Marina Sajid; Waseem Khalid; Zaira Aziz; Muhammad Zubair Khalid; Sulaiman Ali Alharbi; Mohammad Javed Ansari; Abdellah Zinedine; Elena Bartkiene; et al. (Advances in Traditional Medicine, 2026)
Polycystic ovary syndrome (PCOS) is a multifactorial endocrinological and metabolic disorder that affects women of reproductive age. It is often associated with hyperandrogenism, obesity, anovulation, infertility and insulin resistance. In this study, the imminent efficacy of MoLP ( Moringa oleifera leaf powder) and MoLE ( M. oleifera leaf extract) in treating PCOS in female albino mice was explored. Female albino mice were injected with testosterone enanthate [1.0 mg/100 g body weight (b.w.)] for 35-days to induce PCOS. For the treatment, mice were administered with M. oleifera leaf powder (250 and 500 mg/kg b.w.), M. oleifera leaf extract (250 and 500 mg/kg b.w.), and metformin (250 mg/kg b.w.) for 14 days. Following the intervention, body weight, blood glucose, c-peptide, testosterone, follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels and stages of the estrus cycle were measured at 0, 7 and 14 days. The ovaries were examined stereologically to determine the number and diameter of follicles. Results indicated that MoLP, MoLE (500 mg/kg b.w.) and metformin (250 mg/kg b.w.) significantly decreased body weight, blood glucose, c-peptide, testosterone and LH levels while increasing FSH levels and ovary weight over time compared to PCOS-induced mice. Additionally, regulation of the estrus cycle and folliculogenesis in PCOS-induced mice was observed. Overall, the present study revealed that M. oleifera may have the potential as a therapeutic intervention for PCOS. Graphical Abstract

Health risk evaluation of toxic metals in food crops irrigated with wastewater of Hattar Industrial Estate, Pakistan: a simulated gastrointestinal model approach - Ummama Khan; Rukhsanda Aziz; Muhammad Arshad; Basharat Ali; Muhammad Suhaib; Muhammad Tariq Rafiq (Environmental Monitoring and Assessment, 2026)

De novo transcriptome sequencing of Artemisia absinthium predicted anti-SARS-CoV2 (COVID-19) bioactive secondary metabolites - Umar Khitab Khan; Awais Ali; Syed Luqman Ali; Shahid Aziz; Asifullah Khan; Nusrat Shafiq; Bushra Shakoor; Matheus Finger Ramos de Oliveira (Plant Biosystems, 2026)

Molecular characterization of begomoviruses infecting diverse plant species in Swat, Khyber Pakhtunkhwa, Pakistan - Asad Ullah; Aziz Ud Din; Saleem Ur Rahman; Prabu Gnanasekaran; Ying Zhai; Murad Ali Rahat; Hanu R. Pappu; Nisar Ahmad; Fazal Akbar (Australasian Plant Pathology, 2026)

Marine Drug Design for Epitheliocytis Rendering AI ‐Assisted Bioisosteric Replacement of Salicin - Muhammad Naveed; Khushbakht Javed; Tariq Aziz; Rahmana Wazir; Imran Ali; Ayaz Ali Khan; Ashwag Shami; Maher S. Alwethaynani; Fahad Al‐Asmari; Fakhria A. Al‐Joufi (Journal of Fish Diseases, 2026)
Epitheliocystis is a distinctive and relatively understudied bacterial infection of finfish skin and gill epithelia that occurs intracellularly and results in the enlargement of the host cells. The Candidatus Syngnamydia salmonis is a bacterial pathogen that affects fish, especially salmon species like trout and salmon. The production of Epitheliocystis by Candidatus Syngnamydia salmonis poses several challenges to the aquaculture industry. Currently, limited drugs and therapies are available to effectively manage and cease the spread of this disease. The goal of this study was to develop a potential drug target for the treatment of epitheliocystis. Salicin, an organic glucoside widely known for its anti‐inflammatory characteristics, was chosen as the initial compound because of its pharmacological significance and confirmed as a bioisostere (a compound with identical biological activities but a different structure). The Xundrug MolOpt AI generative model of bioisosteric replacement tool was chosen as the optimisation technique in a cognitive exertion to improve the novel drug candidate salicin by its AI‐assisted bioisosteric replacement. To retrieve the docking results, the top three ligands from Xundrug and the cell division protein of Candidatus Syngnamydia salmonis were uploaded to the HDOCK web server, which utilises a hybrid docking technique combining template‐based modelling for docking. The target drug candidate was selected based on model 17's highest docking score of 135.6 kcal/mol. Furthermore, the Lipinski rule of five and the ADMET properties of the Bioisosteric Replaced Salicin model 17 (BRS‐17) were carefully explored. The results showed that BRS‐17 fulfilled the pharmacophore characteristics criteria, hence making it an ideal target candidate for Candidatus Syngnamydia salmonis' cell division protein. Additionally, the results are supported by −6.735Kcal/mol docking score predicted by DockThor. With the help of the supporting information from this study, the proposed drug design can close the gap in earlier studies for resistance to antibiotic treatments. It is suggested that in vitro tests be performed on this drug to show the effectiveness of the suggested design.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Exploring microbiological transformation of glutamate to γ-aminobutyric acid unleashed by a potential Lactobacillus spp. isolated from commercial cheese samples - Sikander Ali; Taha Shafi; Iram Liaqat; Muhammad Usman Ahmad; Ifrah Shabbir; Tariq Aziz; Maha Alharbi; Ashwag Shami; Fahad Al-Asmari; Ibrahim Faisal Halawani; Abdullah A. Alqasem; Reham M. Mashat; et al. (International Dairy Journal, 2026)

New insights into the potential effects of date palm seed powder supplementation on the growth, hemato-biochemical indices, organ histology, and gene expression in Rahmani sheep - Hesham S. Ghazzawy; Nashi K. Alqahtani; Roshmon Thomas Mathew; Hassan M. Ali-Dinar; Osama H. Mahmoud Hassan; Hebatallah M. Saad; Yasmin M. Abd El-Aziz; Ehab El-Haroun; Moaheda E.H. Eissa; El-Sayed Hemdan Eissa (Tropical Animal Health and Production, 2026)

Real-time ultrasound and RGB imaging integration for non-invasive prediction of ribeye area in Tropical Crossbred Brahman Cattle - Nurul Nuraliya Shahrai; Salma Mohamad Yusop; Maimunah Mohd Ali; Mohd Hanis Mohd Saim; Ahmad Rodzian Pok Abdul Aziz; Muhamad Hidayat Mohd Hashim; Shuji Ueda (Tropical Animal Health and Production, 2026)

Comparative assessment of antibacterial, antifungal, and cytotoxic activities of ceragenins CSA-44 and CSA-131 against endodontic pathogens - Kubra Aslantas; Cihan Oz; Ali Taghizadehghalehjoughi; Sidika Genc; Aziz Sahin Erdogan; Paul B. Savage; Mehmet Cemal Adiguzel (Folia Microbiologica, 2025)

Alleviating stocking density stress in juvenile rainbow trout (Oncorhynchus mykiss) through dietary nano-selenium: Effects on growth, antioxidant activity, and immune response - Mashooq Ali; Aqsa Akram; Farid Ahmad Jan; Aziz Ahmad; Ashiq Hussain; Fahim Ullah Khan; Muhammad Arshad (Journal of Trace Elements in Medicine and Biology, 2025)

Camel whey protein coated metal-organic frameworks (CWP/MOF) as a sustainable approach to treat environmental stress-induced liver toxicity by cobalt chloride in rats - Dalia Hamad; Asmaa F.A. Dawood; Hanan M. Alharbi; Shereen Mahmoud Refaie; Marwa A. Ali; A.A. Abu-Sehly; Hanem S. Abdel –Tawab; Nermeen N. Welson; Fatma El-Zahraa A. Abd El-Aziz (Journal of Trace Elements in Medicine and Biology, 2025)

Transformation of wet chemically derived ZnGa-LDH to ZnO:GaN nano-alloys for PMS activated wastewater remediation - Yasir Abbas; Kanwal Shabbir; Haider Aziz; Ijaz Hussain; Hafiz M. Adeel Sharif; Muhammad Ahsan Iqbal; Majid Basharat; Haoliang Wang; Niaz Ali Khan (Journal of Environmental Chemical Engineering, 2025)

Thiourea-modified silk cotton carbon as an efficient sulfur host: A green approach for advanced aluminum-sulfur battery - Muhammad Faheem; Arshad Hussain; Ananda Sholeh Rifky Hakim; Muhammad Ali; Abbas Saeed Hakeem; Md. Abdul Aziz (Biomass and Bioenergy, 2025)

Impact of Tannery Effluents on Groundwater Quality and Human Health in Kasur, Pakistan - Mohammad Salman Faisal; Muhammad Awais; Rohina Bashir; Muhammad Bilal Shakoor; Rizwan Aziz; Muhammad Rizwan; Affaq Ali; Simal Akhtar; Noor Fatima (Water, Air, & Soil Pollution, 2025)

The Capability of Glass Fiber Reinforced Pervious Concrete for Purifying Stormwater Runoff by Removing Physicochemical Contaminants - Hnar Ali Karim Al-Jaf; Dillshad Khidhir Bzeni; Shuokr Qarani Aziz (Water, Air, & Soil Pollution, 2025)

Drought Stress in Viticulture: an Update Review of the Effects, Mechanisms, Tolerance Strategies, and Mitigation Approaches - Sabir Iqbal; Essam Elatafi; Komal Tariq; Shahzad Ali; Abdul Hakeem; Li Shaonan; Rana Badar Aziz; Emmie Quiango Mauligen; Jinggui Fang (Journal of Soil Science and Plant Nutrition, 2025)

Experimental Evaluation of Sleeved Rock Bolts for Corrosion Resistance and Load Transfer Performance in Underground Reinforcement - Adel Mottahedi; Naj Aziz; Alex Remennikov; Ali Mirzaghorbanali; Zhenjun Shan (Geotechnical and Geological Engineering, 2025)
Ground reinforcement using rock bolts is critical for long-term stability in underground excavations, but their effectiveness is highly dependent on their resistance to corrosion. While Corrosion Protection Sleeves (CPS) are widely used to mitigate corrosion in steel rock bolts, their mechanical integrity and influence on the overall system’s performance under axial and shear displacement remain unquantified. This study addresses this knowledge gap by conducting a comparative analysis of sleeved versus conventional rock bolts, investigating the influence of the host medium type, and assessing the integrity of the CPS under various loading conditions. The findings revealed that sleeved bolts show a more ductile response in pull-out tests compared to conventional bolts, allowing for greater roof convergence before debonding. This contrasts with conventional bolts, which demonstrate higher initial stiffness and bond strength. It was also found that, during axial loading, the main failure mode was debonding at the grout-CPS interface, which was similar to the previous studies. Furthermore, the study identified a critical shear displacement threshold of around 25 mm, beyond which the CPS shows visible cracking. This finding differs from previous studies that reported higher thresholds. The results also highlighted that the failure mode and load transfer capacity are influenced by the stiffness of the surrounding host medium, a factor that was not assessed sufficiently in the literature. These outcomes have significant implications for the design and maintenance of ground reinforcement systems. They highlight that while CPS enhances corrosion resistance, their mechanical performance is adversely affected by ground deformation. This research provided practical guidance for field engineers, emphasizing the need for a cautious design approach and continuous monitoring of sleeved rock bolts in highly deformable ground conditions. Meanwhile, the results can help engineers establish a guide for inspection routines and replacement strategies to ensure the long-term reliability and safety of underground excavations.

Whole-Genome analysis of Bacillus subtilis MBBL2 genomic characterization and comparative genomics - Hajra Sohail; Muhammad Naveed; Tariq Aziz; Rania Ali El Hadi Mohamed; Fakhria A. Al-Joufi (Functional & Integrative Genomics, 2025)

Utilization of physicochemical approach to propose a strategy for biofilm inhibition - Ajab Khan; Muhammad Aasim; Noor Shad Bibi; Haris Saddique; Hizb Ullah; Zohaib Khan; Umar Aziz; Nadir Zaman Khan; Waqar Ali; Noor Muhammad (Biofouling, 2025)

Protective effects of whey camel milk proteins conjugate with metal–organic frameworks (MOF) as antimicrobial and against cobalt-induced chloragogen cell toxicity in earthworms - Fatma El-Zahraa Abd El-Aziz; Asmaa F. A. Dawood; Mervat Abdel-Baseer Tohamy Abd El-Aziz; Marwa A. Ali; Hanan A. Ahmed; Rana A. Elbeshbeishy; Rabab M. Thabit; Nermeen Welson; Dalia A. Hamad (Natural Product Research, 2025)

Aspergillus spp and aflatoxins in Pakistani rice: A case study on the decontamination effect of accelerated aging and improved storage practices - Iqra Naeem; Amir Ismail; Yun Yun Gong; Muhammad Riaz; Aneela Hameed; Mubashir Aziz; Asif Mahmood; Waheed Al Masry; Muhammad Latif; Sher Ali; Carlos Augusto Fernandes de Oliveira (Toxicon, 2025)

Covalent organic framework solid-phase microextraction fiber for in vivo monitoring of substituted p-phenylenediamine quinones in fish - Wenhua Ji; Yue Li; Lidan Zhang; Rongyu Wang; Paizu Zhang; Ibragimov Aziz Bakhtiyarovich; Adizov Bobirjon Zamirovich; Iftikhar Ali (Analytica Chimica Acta, 2025)

Variation in the Molecular Phenotype of βglu‐1 , an Insect Defence‐Related Beta‐Glucosidase Gene, in Two Transcontinental Picea Species - Ernest T. Y. Wu; Tin Hang Hung; Nadir Erbilgin; Aziz Ullah; Āris Jansons; Hisham A. A. Ali; Sonya M. Clegg; John J. MacKay (Molecular Ecology, 2025)
Forest trees face threats from many insect pest species, underscoring the importance of understanding their defence mechanisms for survival. In a North American conifer species, Picea glauca , gene expression of β glu‐1 produces phenolic compounds (acetophenones) that defend against its insect defoliator, Choristoneura fumiferana . β glu‐1 is also expressed in a Eurasian conifer species, Picea abies , although no major insect defoliators are present within the species' natural range. We compared the range‐wide variation of β glu‐1 transcript levels from foliage samples of P. glauca in North America and P. abies in Europe using RT‐qPCR and targeted transcriptome sequencing. β glu‐1 transcript levels were highly correlated between the two methods, with large transcript level variation being detected within and between populations in both species and one of the β glu‐1 gene forms being significantly differentially expressed in P. glauca . Importantly, β glu‐1 transcript levels in P. glauca varied longitudinally and were positively associated with mean annual precipitation and C. fumiferana outbreak class, which has historically higher outbreak frequency and severity in eastern compared to western populations. In P. abies , β glu‐1 transcript levels were associated with annual temperature range. Overall, these results enhance our understanding of potential adaptive variation in acetophenone defences in P. glauca , while the factors influencing β glu‐1 transcript variation in P. abies require further investigation.

A combined multi-statistical strategy for mapping groundwater spring potential in northeastern Iraq - Rebar Aziz Qaradaghy; Diary Ali Al-Manmi; Dara Faeq Hamamin (Acta Geophysica, 2025)

Robust vibration control of a barge-type floating offshore wind turbine with a rotational-translational actuator - Syed Awais Ali Shah; Shuanghe Yu; Nadir Abbas; Aziz Noor; Rashid Iqbal (Ocean Engineering, 2025)

Development of novel ferrocene-functionalized NH2-MIL-125 MOF for efficient photocatalytic degradation of indigoid dyes under visible light - Mostafa A. Sayed; Osama A.S. Rafea; Ali M. Abdel-Aziz; Reda M. Abdelhameed; Ibrahim H.A. Badr (Journal of Environmental Chemical Engineering, 2025)

Hybrid modeling of deep neural networks and unsupervised machine learning algorithms for missing well log prediction based on geological lithofacies similarities - Wakeel Hussain; Miao Luo; Muhammad Ali; Izhar Sadiq; Erasto E. Kasala; Tariq Aziz; Zuriyat Batool (Journal of Applied Geophysics, 2025)

Correction to: A flavonoid Ombuin ameliorates thioacetamide-mediated liver cirrhosis in vivo: biochemical, immunohistochemical, inflammatory approaches - Khaled Abdul-Aziz Ahmed; Talal Salem Al-Qaisi; Ahmed A.j. Jabbar; Parween Abdul-Samad Ismail; Mohammed M. Hussein M. Raouf; Hanan Ibrahim Althagbi; Bassam Ali Abed Wahab; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Ahmed Hameed Al-Dabhawi; Musher Ismael Saleh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

A flavonoid Ombuin ameliorates thioacetamide-mediated liver cirrhosis in vivo: biochemical, immunohistochemical, inflammatory approaches - Khaled Abdul-Aziz Ahmed; Talal Salem Al-Qaisi; Ahmed A.j. Jabbar; Parween Abdul-Samad Ismail; Mohammed M. Hussein M. Raouf; Hanan Ibrahim Althagbi; Bassam Ali Abed Wahab; Rawaz Rizgar Hassan; Mahmood Ameen Abdulla; Ahmed Hameed Al-Dabhawi; Musher Ismael Saleh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Facile construction of chitosan-ternary metal selenide biopolymer-based composite for photocatalytic degradation of petroleum derive sunset yellow and acid black azo-dyes using response surface methodology RSM - Tariq Aziz; Muhammad Farhan; Adnan Khan; Nisar Ali; Javeed Azam; Sumeet Malik; Sarmad Ali; Nauman Ali; Hamayun Khan; Rayya Ahmed Al Balushi; Mohammad M. Al-Hinaai; Thuraya Al-Harthy (Environmental Science and Pollution Research, 2025)

Effects of replacement of soybean meal with fermented soybean meal on growth performance, nutrient digestibility and carcass characteristics in broiler - Ali Husnain; Urooj Anwar; Asfa Fatima; Riaz Mustafa; Umar Farooq; Waseem Abbas; Muhammad Farooq Khalid; Muhammad Ashraf; Muhammad Aziz ur Rahman (Livestock Science, 2025)

A geothermal multigeneration system integrating an ORC configuration with an open-feed heater for electricity/H2/cooling production: Techno-economic optimization using a genetic algorithm - Lel Chang; Ali Basem; Ahmad Almadhor; Dyana Aziz Bayz; Sarminah Samad; Mohamed Ayadi; Essam R. El-Zahar; Barno Abdullaeva; Abdulrahman Alansari; H.Elhosiny Ali (International Journal of Refrigeration, 2025)

Inactivation mechanisms of carvacrol on Salmonella Typhimurium and its combined inhibitory effects with blue light-405 nm for chicken meat preservation - Haiying Cui; Xingjun Chen; Tariq Aziz; Rania Ali El Hadi Mohamed; Fahad Al-Asmari; Jaza Maqbl Alshammari; Fakhria A. Al-Joufi; Ce Shi; Lin Lin (International Journal of Food Microbiology, 2025)

Isolation, Identification, biochemical and molecular characterization of potential source of enterotoxigenic strains of Staphylococcus aureus from the bovine raw and mastitis milk - Sikander Ali; Farzana Nazir; Muhammad Usman Ahmad; Hira Sarfraz; Abid Sarwar; Tariq Aziz; Ashwag Shami; Fahad Al-Asmari; Areej A. Alhhazmi; Abeer M. Alghamdi; Fakhria A. Al-Joufi (International Dairy Journal, 2025)

Rare earth metal promoters (La, Ce, Nd, Sm) on nickel-supported Al2O3 catalysts for ammonia decomposition - Mohammad Usman; Ahsan Ali; Abdesslem Jedidi; Afnan Ajeebi; Mohammad Mozahar Hossain; Khalifa M. Yau; Huda Alghamdi; Md. Abdul Aziz; M. Nasiruzzaman Shaikh (Fuel, 2025)

Not All Stroop-Type Tasks Are Alike: Assessing the Impact of Stimulus Material, Task Design, and Cognitive Demand via Meta-analyses Across Neuroimaging Studies - Veronika I. Müller; Edna C. Cieslik; Linda Ficco; Sandra Tyralla; Amir Ali Sepehry; Taraneh Aziz-Safaie; Chunliang Feng; Simon B. Eickhoff; Robert Langner (Neuropsychology Review, 2025)
The Stroop effect is one of the most often studied examples of cognitive conflict processing. Over time, many variants of the classic Stroop task were used, including versions with different stimulus material, control conditions, presentation design, and combinations with additional cognitive demands. The neural and behavioral impact of this experimental variety, however, has never been systematically assessed. We used activation likelihood meta-analysis to summarize neuroimaging findings with Stroop-type tasks and to investigate whether involvement of the multiple-demand network (anterior insula, lateral frontal cortex, intraparietal sulcus, superior/inferior parietal lobules, midcingulate cortex, and pre-supplementary motor area) can be attributed to resolving some higher-order conflict that all of the tasks have in common, or if aspects that vary between task versions lead to specialization within this network. Across 133 neuroimaging experiments, incongruence processing in the color-word Stroop variant consistently recruited regions of the multiple-demand network, with modulation of spatial convergence by task variants. In addition, the neural patterns related to solving Stroop-like interference differed between versions of the task that use different stimulus material, with the only overlap between color-word, emotional picture-word, and other types of stimulus material in the posterior medial frontal cortex and right anterior insula. Follow-up analyses on behavior reported in these studies (in total 164 effect sizes) revealed only little impact of task variations on the mean effect size of reaction time. These results suggest qualitative processing differences among the family of Stroop variants, despite similar task difficulty levels, and should carefully be considered when planning or interpreting Stroop-type neuroimaging experiments.

Fracture analysis and reservoir potential of Jurassic-Paleocene rocks exposed in lower Orakzai area, Lesser Himalayas, Pakistan - Wasif Ullah; Syed Ali Turab; Muhammad Awais Aziz; Nasar Khan (Carbonates and Evaporites, 2025)

Effect of Different Levels of Copper Oxide (CuO) Nanoparticles and Biochar on Soil’s Microbial Activities and Maize (Zea Mays L.) Growth - Muhammad Abdullah Aziz; Sana Zahra; Bilal Adil; Amir Naserin; Muhammad Asad Hameed; Ijaz Ali; Temoor Ahmed; Ajaz Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Exploring Innovative Approaches for Managing Spinal Cord Injury: A Comprehensive Review of Promising Probiotics and Postbiotics - Fereshteh Jamali; Safa Mousavi; Aziz Homayouni-Rad; Ali Meshkini; Hossein Alikhah; Jalil Houshyar; Saba Kamalledin Moghadam; Seyyed Mohammad Yaghoubi; Kimia Motlagh Asghari; Masoud Torbati Ilkhchi; Seyed Ahmad Naseri Alavi (Probiotics and Antimicrobial Proteins, 2025)

Efficacy of Flumetsulam for Post-Emergence Weed Management in Chickpea (Cicer Arietinum L.) Under the Semi-Arid Region of Pakistan - Muhammad Khuram Razzaq; Ali Aziz; Faisal Hayat; Muhammad Zia Ul Haq; Irfan Rasool; Muhammad Naveed Babur; Ali Aslam; Sher Muhammad; Ammara Tahir; Khalid Hussain (Journal of Crop Health, 2025)

An overview of ethnobotanical investigations for primary healthcare: a case study from Mardan district, Pakistan - Muhammad Mohsin; Musheerul Hassan; Ivana Vitasović-Kosić; Mona S. Alwahibi; Sher Wali; Qoryog’diyev Zufar Oxunjonovich; Muhammad Abdul Aziz; M. Ajmal Ali; Rainer W. Bussmann; Arshad Mehmood Abbasi (Plant Biosystems, 2025)

A Critical Review on Development of Laboratory Testing Technologies of Tendons Applied to Stabilize Underground Structures - Adel Mottahedi; Naj Aziz; Alex Remennikov; Ali Mirzaghorbanali; Kevin Marston (Rock Mechanics and Rock Engineering, 2025)
The paper reports on different methods and techniques developed, over the past several decades, to characterize axial and shear strength of various tendons used for ground reinforcement in mining and civil engineering operations. Most of axial loading methods are carried out by pull testing, with very few tests reported on push load tests. Based on an extensive literature survey of more than 80 scientific documents, published between 1970 and 2023, it was shown that a significant number of apparatuses have been developed for testing tendons axially with a limited number being developed for shear testing. The majority of axial testing is undertaken by pull testing tests. The type of tensile strength test selected is dependent on the test purpose and tendon type. The short encapsulation pull test is used mostly for testing solid rebar bolts, while double embedment can be used for the pull testing of both solid rebar and cables, preventing unwinding. A new reverse pull test rig is now available to undertake both the static and dynamic testing of tendons. The single shear and double shear test methods are discussed concerning the different purposes of testing and tendon tool design for the different ground conditions. Several factors and parameters, which influence the effectiveness of bolting, concerning rock reinforcement, are discussed. These factors or parameters include: the medium type and strength, the host medium shape and size of confinement, and the frictional resistance. Particular emphasis is placed on frictionless shear testing of joint faces using the Lateral Truss System (LTS) that prevents shearing faces from coming in contact with each other. The findings from the double shear test indicate that the type of medium, shape and size, and the sheared joint surface of the medium along the applied loading rate all played a prominent role in the determination of the shear test results to achieve effective reinforcement design of the reinforcement system, based on sound calculated parameters for effective ground reinforcement designs and construction. Finally, shear testing of tendons at various angles with respect to rock formation discussed is angle shear testing of tendons installed in large concrete blocks. The paper provides an opportunity for future tests to include the testing and further assessment of tendons studied dynamically to consider reinforcement in seismically active ground.

Recent advances in synthesis of emerging MXenes photocatalysts: A systematic review - Md Mohshin Ali; Md. Arif Hossen; Azrina Abd Aziz (Journal of Environmental Chemical Engineering, 2025)

Burkholderia sp. EIKU24-derived selenium nanoparticles: Characterization, multifunctional bioactivities and their role in sustainable rice cultivation against arsenic stress - Nilendu Basak; Atif Aziz Chowdhury; Sayantani Paul; Taniya Roy; Sk Imran Ali; Ekramul Islam (Biocatalysis and Agricultural Biotechnology, 2025)

The Role of Viral Infections in Acute Kidney Injury and Mesenchymal Stem Cell-Based Therapy - Omer Qutaiba B. Allela; Noor Adel Mohammed Ali; Gaurav Sanghvi; R. Roopashree; Aditya Kashyap; T. Krithiga; Rajashree Panigrahi; Aziz Kubaev; Radhwan Abdul Kareem; Hayder Naji Sameer; Ahmed Yaseen; Zainab H. Athab; et al. (Stem Cell Reviews and Reports, 2025)

Multifaceted effects of climate dynamics and other environmental stressors on women farmers in the Pamir Mountains - Roy C. Sidle; Arnaud Caiserman; Azamat Azarov; Vitalii Zaginaev; Aslam Qadamov; Aziz Ali Khan (Regional Environmental Change, 2025)

Design, synthesis, and computational analysis (molecular docking, DFT, MEP, RDG, ELF) of diazepine and oxazepine sulfonamides: biological evaluation for in vitro and in vivo anti-inflammatory, antimicrobial, and cytotoxicity predictions - Sangar Ali Hassan; Dara Muhammed Aziz; Dana Ali Kader; Shwana Muhamad Rasul; Meer Ali Muhamad; Alla Ahmad Muhammedamin (Molecular Diversity, 2025)

Exploring Nitrogen Use Efficiency in Cereals: Insight into Traits, Metabolism, and Management Strategies Under Climate Change Conditions – A Comprehensive Review - Fatima Zahra Ben Debbane; Aziz Baidani; Maria Aarbaoui; Rachid Moussadek; Rachid Mrabet; Ali Amamou (Journal of Soil Science and Plant Nutrition, 2025)

Effect of Phosphorus Modified Cotton Stick Biochar on Growth, Photosynthesis, Enzymatic Activities and Lead (Pb) Uptake in Tomato Plants Grown in Pb-contaminated Soil - Zaffar Malik; Aleena Shabir; Ahmad Ali; Muhammad Naveed Aslam; Humera Aziz; Syed Farhan Haider Bukhari; Sana Noreen; Usama Ali Tahir; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2025)

Microfacies characterization and diagenetic pathways of the Ordovician to Devonian Setul Group carbonates: implications for homoclinal ramp depositional dynamics in Northern Peninsular Malaysia - Nurul Afifah Mohd Radzir; Mohammad Ezanie Abu Samah; Che Aziz Ali; Kamal Roslan Mohamed (Carbonates and Evaporites, 2025)

Fluoride contamination in plum and peach orchards and its impact on earthworm growth and reproduction - Muhammad Nauman Ahmad; Shah Saud; Afia Zia; Muhammad Baseer Us Salam; Somaira Bibi; Ayaz AlI Khan; Tariq Aziz; Saleh A. Alghamdi; Abdulhakeem S. Alamri; Majid Alhomrani (Environmental Monitoring and Assessment, 2025)

Effects of neem leaf extract on physiochemical traits and antioxidant activity of peach fruit during storage - Jianhui Li; Muhammad Hanif; Muhammad Azam; Muhammad Arslan Khan; Muhammad Ali Umer; Beenish Chaudhary; Imtiaz Hussain; Tariq Aziz Khan; Shoaib ur Rehman; Muhammad Awais; Riadh Ilahy; Hongru Liu; et al. (Journal of Stored Products Research, 2025)

A multi-dimensional approach to assess crop mapping and farmer strategies in drylands of Bamyan, Afghanistan - Arnaud Caiserman; Sayed Muhammad Baqer Hussaini; Aslam Qadamov; Roy C. Sidle; Aziz Ali Khan (Agricultural Systems, 2025)

Sustainable green synthesis of silver nanoparticles for safer biomedical application - Mohammed Ali Dheyab; Azlan Abdul Aziz; Shaymaa Hussein Nowfal; Farhank Saber Braim; Wesam Abdullah; Wasan Hussein Kasasbeh; Mahmood S. Jameel; Saleh T. Alanezi; Mohammad Alrosan; Nazila Oladzadabbasabadi (Journal of Environmental Chemical Engineering, 2025)

Assessment of Climate-resilient Cotton Genotypes Exhibiting High-temperature Tolerance - Sajid Ali; Waqas Shafqat Chattha; Aziz Ullah; Muhammad Zahid Ihsan; Waqar Shafqat; Abdel-Halim Ghazy; Muhammad Afzal; Bilal Ayub (Journal of Crop Health, 2025)

The impact of circadian rhythm disruption on oxaliplatin tolerability and pharmacokinetics in Cry1−/−Cry2−/− mice under constant darkness - Yasemin Kubra Akyel; Narin Ozturk Seyhan; Şeref Gül; Melis Çelik; Ali Cihan Taşkın; Christopher P. Selby; Aziz Sancar; Ibrahim Halil Kavakli; Alper Okyar (Archives of Toxicology, 2025)
Circadian rhythms, the 24-h oscillations of biological activities guided by the molecular clock, play a pivotal role in regulating various physiological processes in organisms. The intricate relationship between the loss of circadian rhythm and its influence on the tolerability and pharmacokinetic properties of anticancer drugs is poorly understood. In our study, we investigated the effects of oxaliplatin, a commonly used anticancer drug, on Cry1 −/− and Cry2 −/− mice ( Cry DKO mice) under darkness conditions, where they exhibit free-running phenotype. We administered oxaliplatin at a dosage of 12 mg/kg/day at two distinct circadian times, CT8 and CT16, under constant darkness conditions to Cry DKO mice and their wild type littermates. Our results revealed a striking disparity in oxaliplatin tolerance between Cry DKO mice and their wild-type counterparts. Oxaliplatin exhibited severe toxicity in Cry DKO mice at both CT8 and CT16, in contrast to the wild type mice. Pharmacokinetic analyses suggested that such toxicity was a result of high concentrations of oxaliplatin in the serum and liver of Cry DKO mice after repeated dose injections. To understand the molecular basis of such intolerance, we performed RNA-seq studies using mouse livers. Our findings from the RNA-seq analysis highlighted the substantial impact of circadian rhythm disruption on gene expression, particularly affecting genes involved in detoxification and xenobiotic metabolism, such as the Gstm gene family. This dysregulation in detoxification pathways in Cry DKO mice likely contributes to the increased toxicity of oxaliplatin. In conclusion, our study highlights the crucial role of an intact molecular clock in dictating the tolerability of oxaliplatin. These findings emphasize the necessity of considering circadian rhythms in the administration of anticancer drugs, providing valuable insights into optimizing treatment strategies for cancer patients.

Phytoremediation potential and ecophysiological responses of Pistia stratiotes L. for removal of cadmium and lead from polluted water: a viable option for agricultural resilience - Sheza Ayaz Khilji; Rabia Tariq; Irfan Aziz; Neelma Munir; Arooj Javed; Tehreem Uppal; Zainul Abideen; Mohamed A. El-Sheikh; Ali El- Keblawy (Environmental Sustainability, 2025)

Innovative circular bioeconomy and decarbonization approaches in palm oil waste management: A review - Kai Chen Goh; Tonni Agustiono Kurniawan; G. Abdulkareem AlSultan; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Faissal Aziz; Imran Ali; Joan Cecilia C. Casila; Muhammad Imran Khan; Dongdong Zhang; Choo Wou Onn; Ta Wee Seow; et al. (Process Safety and Environmental Protection, 2025)

Reinforcing urban resilience through sound landfill management: Addressing global climatic challenges with novel solutions - Kai Chen Goh; Tonni Agustiono Kurniawan; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Faissal Aziz; Imran Ali; Joan Cecilia C. Casila; Muhammad Imran Khan; Dongdong Zhang; Wei Dai; Choo Wou Onn; Ta Wee Seow (Process Safety and Environmental Protection, 2025)

Design of a peristaltic pump-based feeding device for achieving continuous production in food 3D printing - Lin Lin; Yuhuan Duan; Tariq Aziz; Ashwag Shami; Fahad Al-Asmari; Rania Ali El Hadi Mohamed; Haiying Cui (Innovative Food Science & Emerging Technologies, 2025)

Unveiling Axial Load Transfer Mechanism in Fully Encapsulated Rock Bolts - Hadi Nourizadeh; Ali Mirzaghorbanali; Kevin McDougall; Hani Mitri; Peter Craig; Ashakan Rastegarmanesh; Naj Aziz (Rock Mechanics and Rock Engineering, 2025)
Determining the axial load transfer mechanism of rock bolts under various conditions is paramount for ensuring efficient reinforcement in rock structures, advancing our understanding of rock support and ability to design robust engineering solutions. This paper presents the results of an experimental study aimed at investigating the factors affecting axial load transfer mechanisms in fully encapsulated rock bolts including embedment length, mechanical characteristics of bonding materials, and host rock conditions. The results show that increasing the embedment length improves the pullout capacity, but only up to a critical length, beyond which the ultimate strength and bond stress distribution remain constant. Amongst the mechanical characteristics, shear modulus of the bonding materials was found the most significant factor influencing axial load transfer and the bond stress distribution. Compressive strength of bonding materials, which is commonly used to assess performance, should not be the only factor considered, as shear properties were found more representative. The expansion characteristics of the bonding agents were also found to be effective in improving pullout performance. The study also provides a detailed explanation of how the mechanical properties of host rocks affect the pullout capacity of bolts. Specifically, it states that greater stiffness result in higher pullout strength.

Sulforaphane substantially impedes testicular ferroptosis in adult rats exposed to di-2-ethylhexyl phthalate through activation of NRF-2/SLC7A11/GPX-4 trajectory - Mohammed M. Elseweidy; Nouran G. Harb; Abdelmoniem A. Ali; Reda M. Abd El-Aziz; Rania A. Elrashidy (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Di-2-ethylhexyl phthalate (DEHP) is a common plasticizer with a deleterious impact on testicular functionality and male fertility. Growing evidence implicates ferroptosis as one of the plausible mechanisms for DEHP-induced testicular injury. Sulforaphane (SFN) is a natural isothiocyanate displaying beneficial effects on testicular injury in several animal models. Herein, we explored the potential protective effect of SFN on testicular ferroptosis and toxicity evoked by DEHP. Adult male Wistar rats were equally distributed into three groups ( n = 6/group): (i) CON group; (ii) DEHP group, received DEHP (2 g/kg PO) for 4 weeks; and (iii) DEHP + SFN group, received SFN (10 mg/kg, PO) 1 week prior to DEHP then concurrently with DEHP for further 4 weeks. Compared to CON group, exposure to DEHP caused testicular atrophy, deteriorated testicular architecture, testicular fibrosis, reduced sperm count and motility, higher sperm deformity, and declined serum testosterone level. All these abnormalities were ameliorated by SFN preconditioning. Additionally, pretreatment with SFN reversed the increased aromatase level and upregulated the steroidogenic markers in testes of DEHP-exposed rats. SFN pretreatment also counteracted DEHP-induced oxidative stress and boosted the total antioxidant capacity in testicular tissue via activation of the nuclear factor erythroid 2-related factor 2 (NRF-2) and its downstream target, hemeoxygenase-1 (HO-1). Moreover, SFN preconditioning mitigated DEHP-induced ferroptosis through up-surging SLC7A11, GPX-4, and GSH, while suppressing iron overload and ACSL4-induced lipid peroxidation in testicular tissue of rats. These findings may nominate SFN as a promising protective intervention to alleviate testicular ferroptosis associated with DEHP exposure through activation of NRF-2/SLC7A11/GPX-4 trajectory.

Production Optimization and Potential Bioactivities of Biosurfactant from PET Surface-Dwelling Oligotrophic Bacillus sp. EIKU23 - Atif Aziz Chowdhury; Nilendu Basak; Taniya Roy; Sayantani Paul; Ajar Nath Yadav; Sk Imran Ali; Ekramul Islam (Current Microbiology, 2025)

Effects of dietary organic selenium, vitamin C, and vitamin E supplementation on growth performance, serum biochemistry, and antioxidant status in juvenile Hypophthalmichthys molitrix - Hairui Yu; Maida Mushtaq; Saira Razzaq; Umar Ali; Muhammad Khan; Abdur Rahman; Guobo Quan; Mehroze Fatima; Saima Naveed; Muhammad Hammad Zafar; Muhammad Aziz ur Rahman (Frontiers in Marine Science, 2025)
The study aimed to evaluate the effects of dietary supplementation of selenium (Se), vitamin C, and vitamin E on growth performance, meat quality, and antioxidant status in Hypophthalmichthys molitrix juveniles. A total of 480 juveniles (mean weight: 20 ± 0.29 g) were randomly assigned to 24 aquaria (20 fish per 100 L), which were allocated to eight dietary treatments (three aquaria per treatment) following a completely randomized design. The dietary treatments included: (1) a basal diet without supplementation (Control), (2) selenium supplementation (S), (3) vitamin C supplementation (C), (4) vitamin E supplementation (E), (5) selenium and vitamin C supplementation (SC), (6) selenium and vitamin E supplementation (SE), (7) vitamin C and vitamin E supplementation (EC), and (8) selenium, vitamin C, and vitamin E supplementation (SCE). The supplementation levels were 0.9 mg/kg Se, 300 mg/kg vitamin C, and 100 mg/kg vitamin E, respectively. After a one-week acclimatization period, a 10-week growth trial was conducted. Fish fed the SCE diet exhibited significantly higher (p< 0.05) final weight gain, body length gain, body weight gain percentage, and specific growth rates compared to other treatments. Selenium concentrations in the kidney, liver, pancreas, and muscle were significantly higher (p< 0.05) in the SCE, SC, SE, and EC groups compared to the Control and single-supplement groups. Hematological parameters, including WBC, RBC, HGB, HCT, and MCHC, were significantly higher (p< 0.05) in the SCE group compared to all other groups. Similarly, serum activities of ALT, AST, and ALP were significantly lower (p< 0.05) in the SCE group than in other treatments, while blood glucose levels were unaffected (p > 0.05) by dietary treatments. Antioxidant enzyme activities, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), were significantly enhanced (p< 0.05) in the whole body and muscle tissues of fish receiving Se, vitamin C, and E supplementation. Thiobarbituric acid reactive substances (TBARS) levels in muscle and serum were significantly higher (p< 0.05) in the Control group compared to all supplemented groups. The proximate composition of meat, including dry matter, fat, ash, and protein contents, was not significantly affected (p > 0.05) by the dietary treatments. In conclusion, dietary supplementation of selenium, vitamin C, and vitamin E significantly improved growth performance, selenium deposition in tissues, and antioxidant status of Hypophthalmichthys molitrix juveniles, without adversely affecting meat chemical composition.

In-vitro and in-vivo assessments of greenly synthesized iron oxide nanoparticles from Cascabela thevetia plant extract for the treatment of ventricular septal defect - Amina Abid; Muhammad Naveed; Tariq Aziz; Muhammad Aqib Shabbir; Hira Mubeen; Ayaz Ali Khan; Abdullah F Alsmari (South African Journal of Botany, 2025)

Physio-biochemical and molecular mechanisms of low nitrogen stress tolerance in peanut (Arachis hypogaea L.) - Xiangjun Kong; Rui Wang; Peipei Jia; Hengbin Li; Aziz Khan; Ali Muhammad; Sajid Fiaz; Qunce Xing; Zhiyong Zhang (Plant Molecular Biology, 2025)

Possible protective effects of vanillin against stress-induced seminiferous tubule injury via modulation of Nrf2 and ZO1 - Sara Mohamed Naguib Abdel Hafez; Entesar Ali Saber; Neven Makram Aziz; Mohammed Mustafa Abd El Aleem; Manar Samir Mohamed; Elshimaa M. N. Abdelhafez; Randa Ahmed Ibrahim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Around 20% of the human population is distressed. Previous studies have looked into the relationship between restraint immobilization stress (IS) and sexual behavior in male rats. The current study aimed to provide a brief explanation of the mechanisms that generated testicular injury with chronic IS and an attempt to evaluate the mechanisms and effects of vanillin as a novel protective agent. Forty-eight adult male albino rats were divided into six groups: control, vanillin-treated, chronic 2-h IS, 2-h stressed-vanillin-treated, chronic 6-h IS, and 6-h stressed-vanillin treated. The rats were sacrificed, and blood samples were collected for biochemical study. The testes were processed for biochemical and histological study, as well as histological Johnsen score. The results showed that prolonged IS increased both corticosterone and TNF-α levels as well as decreased testosterone, luteinizing hormone, catalase, and Nrf2 levels. This effect was more pronounced after 6 h of IS compared to 2 h. It also induced various testicular injuries with weak ZO-1 and CD34 immunoreactions. On the contrary, vanillin improved all mentioned biochemical and histological alternations induced by stress. Additionally, computational molecular docking analyses were conducted on the compound vanillin within the active site of Zona Occludens-1 (PDB ID: 2JWE). The results demonstrated remarkable docking scores and binding affinity, corroborating its potential protective efficacy. It could be concluded that vanillin is a promising treatment alternative for protecting testicular tissue from the harmful effects of IS via its antioxidant and anti-inflammatory properties.

Performance of Cable Bolts in Small- and Large-Scale Laboratory Pullout Tests - Ashkan Rastegarmanesh; Ali Mirzaghorbanali; Kevin McDougall; Naj Aziz; Sina Anzanpour; Hadi Nourizadeh (Geotechnical and Geological Engineering, 2025)

Cost-effectiveness of rivaroxaban plus aspirin versus aspirin alone in patients with stable coronary artery disease or peripheral artery disease: a systematic review - Jalal Arabloo; Mohammad Ali Rezaei; Vahid Makhtoumi; Zahra Mollaei Sadiani; Aziz Rezapour (European Journal of Clinical Pharmacology, 2025)

Enhanced simultaneous voltammetric detection of lead, copper, and mercury using a MIL-101(Cr)-(COOH)2@MWCNTs modified glassy carbon electrode - Osama A.S. Rafea; Ali M. Abdel-Aziz; Mostafa A. Sayed; Reda M. Abdelhameed; Ibrahim H.A. Badr (Analytica Chimica Acta, 2025)

Exploring the axial performance of protective sheathed rock bolts through large-scale testing - Hadi Nourizadeh; Ali Mirzaghorbanali; Kevin McDougall; Naj Aziz (Tunnelling and Underground Space Technology, 2025)

Innovative transformation of palm oil biomass waste into sustainable biofuel: Technological breakthroughs and future prospects - Tonni Agustiono Kurniawan; Mehwish Ali; Ayesha Mohyuddin; Ahtisham Haider; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Hui Hwang Goh; Dongdong Zhang; Wei Dai; Faissal Aziz; Muhammad Imran Khan; Imran Ali; et al. (Process Safety and Environmental Protection, 2025)

Black Seed Oil-Based Curcumin Nanoformulations Ameliorated Cuprizone-Induced Demyelination in the Mouse Hippocampus - Mohammad Zubair Alam; Hala Abubaker Bagabir; Mohammad Alameen Faisal Zaher; Thamer M. A. Alqurashi; Badrah S. Alghamdi; Mohsin Kazi; Ghulam Md Ashraf; Gadah Ali Alshahrany; Noor Ahmed Alzahrani; Rafal Mohammed Bakhalgi; Juweiriya; Mona Al-Thepyani; et al. (Molecular Neurobiology, 2025)

Correction to: The effects of nano‑selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El‑Aziz; Yasmin A. Reyad; El‑Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

The effects of nano-selenium and/or vitamin C on the growth performance, blood health, organ histology, molecular alterations, and disease resistance of Nile tilapia (Oreochromis niloticus) against Saprolegnia ferax - Hayat Ali Alafari; Najah M. Albaqami; Yasmin M. Abd El-Aziz; Yasmin A. Reyad; El-Sayed Hemdan Eissa; Zulhisyam Abdul Kari; Moaheda E. H. Eissa; Saadiah Ibrahim; Saleha Khan; Mohammad Bodrul Munir; Abdelazeem M. Algammal; Ismail Youssef; et al. (Aquaculture International, 2025)

Chemical modification of Pinus walliichiana sawdust: Application in membrane system for efficient purification of groundwater containing Cd(II) and Ni(II) - Muhammad Imran Irfan; Mahnoor Sadiq; Lubna Zohra; Abu Bakar Siddique; Muhammad Yousaf; Madiha Rubab; Kishwar Urooj; Ambreen Aziz; Hira Ali; Mehreen Fatima; Hatem M.A. Amin; Hassan A. Alhazmi; et al. (Journal of Water Process Engineering, 2024)

Nanoformulation of imidacloprid insecticide with biocompatible materials and its ecological and physiological effects on wheat green aphid, Schizaphis graminum Rondani - Roya Ahmadpour; Hooshang Rafiee Dastjerdi; Ali Golizadeh; Aziz Habibi Yangjeh; Zahra Abedi; Vahid Mahdavi (Journal of Asia-Pacific Entomology, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Comparative genomics and evolutionary analysis of dengue virus strains circulating in Pakistan - Aziz Ul-Rahman; Muhammad Zubair Shabbir; Majeeda Rasheed; Nusrat Shafi; Kalsoom AbdulRazaq; Hamna Ramzan; Rauf Mehmood; Junaid Ali Khan (Virus Genes, 2024)

Catalytic synthesis of selenium nanoparticles by gram-negative Aeromonas sobria and their application for removal of toxic dyes - Soma Sardar Barawi; Karzan Ahmed Qurbani; Seenaa Muhammed Ali; Safin Hassan Hussein; Dara Muhammed Aziz; Rawezh Omer Hamasalih; Razhan Bakhtyar Ahmed; Haider Mousa Hamzah (Biologia, 2024)

Small scale laboratory monotonic and cyclic pull out testing on grout and resin encapsulated cable bolts - Ashkan Rastegarmanesh; Ali Mirzaghorbanali; Kevin McDougall; Naj Aziz; Sina Anzanpour; Hadi Nourizadeh; Mahdi Moosavi (International Journal of Rock Mechanics and Mining Sciences, 2024)

Analysing Double Shearing Mechanism in Fiberglass Rock Bolting Systems: a Comprehensive Analytical Model and Numerical Simulation Approach - Peter Gregor; Ali Mirzaghorbanali; Kevin McDougall; Naj Aziz; Behshad Jodeiri Shokri; Hadi Nourizadeh; Abbas Taheri (Geotechnical and Geological Engineering, 2024)
An analytical method and numerical simulation were developed to investigate the shear performance of fiberglass rock bolts (20-tonne and 30-tonne) by conducting sixteen double-shearing tests with both clean and infilled shear interfaces. Following the preparation of the required samples, each test set-up was subjected to different ranges of pretension values. The infilled scenario involved 5 mm thick sandy clay infilled shear interfaces. The results of the double shearing tests unveiled that as pretension increased, so did the confining pressures at the shear interfaces for both clean and infilled joints. Also, an analytical model was developed utilising the Fourier transform, energy balance theory, and linear elastic theory. The result was an empirical relationship that could determine the double shear performance of fibreglass rock bolts in close agreement with the experimental data. Coefficients were incorporated to facilitate model calibration and tuning. Eventually, fast Lagrangian analysis of continua (FLAC) three-dimensional (3D) modelling was utilised to conduct numerical simulations of fibreglass rock bolts subjected to double shearing scenarios. The numerical model was calibrated against experimental data and then extended to conduct a sensitivity analysis on fibreglass rock bolts subjected to double shear test setup variations. Scenarios included rock bolt installation angles, shearing rates, and various host rock strengths. The results revealed that increasing the shear speed from the experimental test baseline yielded substantial displacement increases in the post-failure residual performance of the rock bolts. Changing the installation angle resulted in greater peak shear forces and extended residual zones. The least significant impacts were observed when changing the host rock UCS, suggesting neither rock bolt was drastically impacted by weak or strong host rocks.

The importance of sharing: wild plant knowledge in three valleys of Northern Pakistan - Adnan Ali Shah; Abid Raza; Naji Sulaiman; Dipak Khadka; Abdul Majid; Muhammad Abdul Aziz; Arshad Mehmood Abbasi; Mushtaq Ahmad; Andrea Pieroni (Plant Biosystems, 2024)

Non-coding RNAs as a Critical Player in the Regulation of Inflammasome in Inflammatory Bowel Diseases; Emphasize on lncRNAs - Hussein salim abed; Enwa Felix Oghenemaro; Aziz Kubaev; Zuhair Mohammed Ali Jeddoa; RenukaJyothi S; Shilpa Sharma; Raghav Vashishth; Majid S. Jabir; Sabrean Farhan Jawad; Ahmed Hussein Zwamel (Cell Biochemistry and Biophysics, 2024)

Antibacterial Efficacy of Tryptophan Coordinated Silver Nanoparticles Against E. coli: Spectroscopic and Microscopic Evaluation of Bacterial Cell Death - Rafaqat Ali Khan; Shahzad Anwar; Hina Ali; Uzma Aziz; Bisma Khanam; Muhammad Zakria; Muhammad Raffi (Journal of Fluorescence, 2024)

Pluvial flood modeling for coastal areas under future climate change – A case study for Prince Edward Island, Canada - Quan Van Dau; Xiuquan Wang; Farhan Aziz; Rana Ali Nawaz; Tianze Pang; Muhammad Qasim Mahmood; Maxim Fortin (Journal of Hydrology, 2024)

Dynamic interplay of silica-coated iron oxide nanocomposite on soil-plant system to mitigate Cd toxicity in rice - Faisal Islam; Muhammad Saad Shoaib Khan; Sulaiman Ahmed; Aziz Ul Ikram; Fakhir Hannan; Mehmood Jan; Muhammad Sajid; Ali Ahmed Zaky Shoaib; Shan Liu; Jian Chen (Journal of Cleaner Production, 2024)

Advancements in nanotechnology applications: Transforming catalysts, sensors, and coatings in petrochemical industries - Ar Rafi Ferdous; Syed Niaz Ali Shah; Syed Shaheen Shah; Md. Abdul Aziz (Fuel, 2024)

Smartphone-assimilated colorimetric sensor for sub-nanomolar emamectin detection via KA30 capped silver nanoparticles in food, bio-fluids and water samples - Aziz Balouch; Kashif Hussain; Ayman Nafady; Abdul Jabbar; Sufian Rasheed; Sumaira Kanwal; Sadia Haider; Razium Ali Soomro; Sirajuddin; Muhammad Raza Shah (Food Chemistry, 2024)

From problem to progress: Rodent management in agricultural settings of sub-Saharan Africa and calling for an urban perspective - Ambroise Dalecky; Ibrahima Sow; Abdoul Aziz Ibrahim Danzabarma; Madougou Garba; Jonas Etougbétché; Sylvestre Badou; Henri-Joël Dossou; Cheikh Tidiane Niang; Ousmane Diene; Idrissa Diallo; Mohamed Seyidna Ali Saghiri; Mohamed El Hady Sidatt; et al. (Crop Protection, 2024)

Cultivating sustainability: Harnessing biochar-derived composites for carbon-neutral wastewater treatment - Tonni Agustiono Kurniawan; Shahnoor Ali; Ayesha Mohyuddin; Ahtisham Haider; Mamoona Riaz; Sajid Khan; Mohd Hafiz Dzarfan Othman; Hui Hwang Goh; Abdelkader Anouzla; Faissal Aziz; Imran Ali (Process Safety and Environmental Protection, 2024)

Paleoclimate changes across the Cenomanian–Santonian transition at the southern Neo-Tethys margin (SW Iran): An integrated approach - Aziz Abdolahi; Mohammad Bahrehvar; Hamzeh Mehrabi; Mahboobeh Omidvar; Ali Kadkhodaie; David A. Wood (Gondwana Research, 2024)

Aflatoxins in the rice production chain: A review on prevalence, detection, and decontamination strategies - Iqra Naeem; Amir Ismail; Muhammad Riaz; Mubashir Aziz; Kashif Akram; Muhammad A. Shahzad; Mavra Ameen; Sher Ali; Carlos A.F. Oliveira (Food Research International, 2024)

Chemical control of wheat sunn pest, Eurygaster integriceps, by UAV sprayer and very low volume knapsack sprayer - Aziz Sheikhigarjan; Mahmoud Safari; Mostafa Mansour Ghazi; Ali Zarnegar; Shahram Shahrokhi; Nikrooz Bagheri; Saeed Moein; Peyman Seyedin (Phytoparasitica, 2024)

Hyperspectral target detection using self-supervised background learning - Muhammad Khizer Ali; Benish Amin; Abdur Rahman Maud; Farrukh Aziz Bhatti; Komal Nain Sukhia; Khurram Khurshid (Advances in Space Research, 2024)

Integrated study of GIS and Remote Sensing to identify potential sites for rainwater harvesting structures - Xingsheng Du; Aqil Tariq; Fakhrul Islam; Samman Aziz; Liaqat Ali Waseem; Muhammad Nasar Ahmad; Muhammad Amin; Naz Ul Amin; Shoaib Ali; Muhammad Aslam; Walid Soufan (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Evaluation of drought hazards and coping strategies adopted by pastoral communities in the Cholistan Rangeland of Pakistan - Muhammad Farooq Azhar; Muhammad Junaid Faiz; Ehsan Ali; Abida Aziz; Muhammad Akbar; Ghulam Raza; Muhammad Abdullah; Muhammad Muzammil Habib; Muhammad Farooq Akram (Environmental Development, 2024)

Solar Light Assisted Metal Selenide-Chitosan Nanoparticles from Structure Tailoring to Photocatalytic Mineralization of Selected Industrial Dyes - Javeed Azam; Muhammad Farhan; Adnan Khan; Tariq Aziz; Nauman Ali; Hamayun Khan; Sumeet Malik; Nisar Ali (Water, Air, & Soil Pollution, 2024)

Protective effects of Chlorella vulgaris as a feed additive on growth performance, immunity, histopathology, and disease resistance against Vibrio parahaemolyticus in the Pacific white shrimp - El-Sayed Hemdan Eissa; Rabab Mohamed Aljarari; Amal Elfeky; Yasmin M. Abd El-Aziz; Mohammad Bodrul Munir; Samyah D. Jastaniah; Bothaina Ali Alaidaroos; Manal E. Shafi; Nadia Nazmy B. Abd El-Hamed; Ammar AL-Farga; Hagar Sedeek Dighiesh; Ekemini Moses Okon; et al. (Aquaculture International, 2024)
The present study investigated the effect of Chlorella vulgaris on growth performance, feed consumption, body composition, and immune response of white shrimp ( Litopenaeus vannamei ) against Vibrio parahaemolyticus infection. Shrimps (4.00 ± 0.04 g) were divided into five groups (3 replicates/20 each) in 15 hapa (1 m 3 ) and cultured for 56 days with five C. vulgaris experimented diets at five different concentrations (0, 15, 20, 25, and 30 g/kg feed). Growth performance, feed utilization, biomass, and body composition (protein, lipid, and ash) were analyzed and revealed significant increase ( P C. vulgaris diet. Additionally, the survival rate of shrimp in all experimental feeds was improved, but was not significant. Shrimp fed with C. vulgaris at different concentrations showed significantly ( P C. vulgaris in the diet showed significantly ( P C. vulgaris might be used to improve growth performance, feed utilization, body composition, and immune biomarker responses, leading to disease resistance in cultured shrimp.

Unlocking synergies between waste management and climate change mitigation to accelerate decarbonization through circular-economy digitalization in Indonesia - Tonni Agustiono Kurniawan; Christia Meidiana; Hui Hwang Goh; Dongdong Zhang; Mohd Hafiz Dzarfan Othman; Faissal Aziz; Abdelkader Anouzla; Prakash Kumar Sarangi; Buntora Pasaribu; Imran Ali (Sustainable Production and Consumption, 2024)

Silicon and Titanium Dioxide Mitigate Copper Stress in Wheat (Triticum aestivum L.) Through Regulating Antioxidant Defense Mechanisms - Rana M. Alshegaihi; Muhammad Hamzah Saleem; Ammara Saleem; Baber Ali; Humera Aziz; Shah Fahad; Abed Alataway; Ahmed Z. Dewidar; Hosam O. Elansary (Journal of Plant Growth Regulation, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

A review on the nanotechnology-based approaches for managing sexually transmitted infections - Alam Zeb; Namrah Khan; Fawad Ali Shah; Aziz Ullah; Ho-Ik Choi; Jeong-Su Ryu; Yumi Bae; Han-Joo Maeng; Wondong Kim; Jin-Ki Kim (Journal of Pharmaceutical Investigation, 2024)

Recent advances of plant-mediated metal nanoparticles: Synthesis, properties, and emerging applications for wastewater treatment - Mohammed Ali Dheyab; Nazila Oladzadabbasabadi; Azlan Abdul Aziz; Pegah Moradi Khaniabadi; Mushtak T.S. Al-ouqaili; Mahmood S. Jameel; Farhank Saber Braim; Baharak Mehrdel; Mehran Ghasemlou (Journal of Environmental Chemical Engineering, 2024)

Effect of different concentrations of resveratrol on nuclear maturation and in-vitro development competence of oocytes of Nili Ravi buffalo - Samar Wafa Kabeer; Amjad Riaz; Aziz Ul-Rahman; Rana Muhammad Shahbakht; Ahsan Anjum; Hafeez ur Rehman Ali Khera; Ali Haider; Faisal Riaz; Riffat Yasin; Muhammad Yaseen; Muhammad Saleem; Naheed Bano; et al. (Tropical Animal Health and Production, 2024)

Silica nanoparticles alleviate the immunosuppression, oxidative stress, biochemical, behavioral, and histopathological alterations induced by Aeromonas veronii infection in African catfish (Clarias gariepinus) - Heba H. Mahboub; Wafaa M. Gad; Enas K. Aziz; Mona Abdelghany Nasr; Esraa M. Fahmy; Dina Mohamed Mansour; Nesma Rasheed; Hanaa S. Ali; Sameh H. Ismail; Afaf N. Abdel Rahman (Fish Physiology and Biochemistry, 2024)
In the aquaculture industry, silica nanoparticles (SiNPs) have great significance, mainly for confronting diseases. Therefore, the present study aims to assess the antibacterial efficiency of SiNPs as a versatile trial against Aeromonas veronii infection in African catfish ( Clarias gariepinus ). Further, we investigated the influence of SiNPs in palliating the immune-antioxidant stress biochemical, ethological, and histopathological alterations induced by A. veronii . The experiment was conducted for 10 days, and about 120 fish were distributed into four groups at random, with 30 fish each. The first group is a control that was neither exposed to infection nor SiNPs. The second group (SiNPs) was vulnerable to SiNPs at a concentration of 20 mg/L in water. The third group was experimentally infected with A. veronii at a concentration of 1.5 × 10 7 CFU/mL. The fourth group ( A. veronii + SiNPs) was exposed to SiNPs and infected with A. veronii . Results outlined that A. veronii infection induced behavioral alterations and suppression of immune-antioxidant responses that appeared as a clear decline in protein profile indices, complement 3, lysozyme activity, glutathione peroxidase, and total antioxidant capacity. The kidney and liver function biomarkers (creatinine, urea, alkaline phosphatase, and alanine aminotransferase) and lipid peroxide (malondialdehyde) were substantially increased in the A. veronii group, with marked histopathological changes and immunohistochemical alterations in these tissues. Interestingly, the exposure to SiNPs resulted in a clear improvement in all measured biomarkers and a noticeable regeneration of the histopathological changes. Overall, it will establish that SiNPs are a new, successful tool for opposing immunological, antioxidant, physiological, and histopathological alterations induced by A. veronii infection.

Natural-based edible nanocomposite coating for beef meat packaging - Mohammad Ali Ghoflgar Ghasemi; Hamed Hamishehkar; Afshin Javadi; Aziz Homayouni-Rad; Hoda Jafarizadeh-Malmiri (Food Chemistry, 2024)

UV-spectrophotometric Optimization of Temperature, pH, Concentration and Time for Eucalyptus Globulus Capped Silver Nanoparticles Synthesis, their Characterization and Evaluation of Biological Applications - Ansar Aziz Subhani; Muhammad Irshad; Shaukat Ali; Muhammad Jawad; Muhammad Faran Akhtar; Muhammad Summer (Journal of Fluorescence, 2024)

Flash flood hazard assessment in the Amlog Valley Basin, North-West Galala City, Egypt, based on a morphometric approach - Mohamed Alkhuzamy Aziz; Ali Hagras (Applied Geomatics, 2024)

An Aedes–Anopheles Vaccine Candidate Supplemented with BCG Epitopes Against the Aedes and Anopheles Genera to Overcome Hypersensitivity to Mosquito Bites - Muhammad Naveed; Urooj Ali; Tariq Aziz; Rida Naveed; Sarmad Mahmood; Muhammad Mustajab Khan; Metab Alharbi; Thamer H. Albekairi; Abdullah F. Alasmari (Acta Parasitologica, 2024)

Assessing the impact of renewable energy and financial development on environment quality in Asian emerging economies (AEEs) - Usman Saleem Yousaf; Farhan Ali; Babar Aziz; Shahzad Hussain; Saima Sawar (Environment, Development and Sustainability, 2024)

Leveraging food waste for electricity: A low-carbon approach in energy sector for mitigating climate change and achieving net zero emission in Hong Kong (China) - Tonni Agustiono Kurniawan; Xue Liang; Hui Hwang Goh; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Hussein E. Al-Hazmi; Kit Wayne Chew; Faissal Aziz; Imran Ali (Journal of Environmental Management, 2024)

Taphonomic damage of molluscan shells in the Nile Delta under natural and anthropogenic sources of environmental variability - Ahmed Awad Abdelhady; Hatem F. Hassan; Basma A.A. Balboul; Khalaf H.M. Abdel-Raheem; Aziz Abu Shama; Mohamed Ahmed; Ali M. Hussain (Journal of African Earth Sciences, 2024)

Higher cadmium and zinc accumulation in parsley (Petroselinum crispum) roots activates its antioxidants defense system - Ismat Nawaz; Atifa Mehboob; Aqib Hassan Ali Khan; Tatheer Alam Naqvi; Nazneen Bangash; Sadia Aziz; Wajiha Khan; Irum Shahzadi; Rocío Barros; Kifayat Ullah; Mohammad Maroof Shah (BioMetals, 2024)

Copolymerization of ethylene and isoprene via silicon bridge metallocene [rac-Me2Si(2-Me-4-Ph-Ind)2ZrCl2] catalyst: A new way to control the composition and microstructure of copolymers - Amjad Ali; Ahmad Naveed; Anna Maroń; Muhammad Adnan Younis; Jamile Mohammadi Moradian; Balal Yousaf; Tariq Aziz; Rai Nauman Ali; Naushad Ahmad; Suliman Yousef Alomar; Fan Zheqiang; Li Guo (Chemosphere, 2024)

Deciphering the Role of Phytohormones and Osmolytes in Plant Tolerance Against Salt Stress: Implications, Possible Cross-Talk, and Prospects - Sadam Hussain; Muhammad Bilal Hafeez; Rabia Azam; Kashf Mehmood; Marjan Aziz; Sezai Ercisli; Talha Javed; Ali Raza; Noreen Zahra; Saddam Hussain; Xiaolong Ren (Journal of Plant Growth Regulation, 2024)

Biochemical profile of Vaucheria karachiensis and evaluation of its nutritional, antioxidant, antimicrobial, and hypoglycemic potentials - Arshad Iqbal; Muhammad Imran; Syed Lal Badshah; Ashwag Shami; Baber Ali; Zamarud Shah; Muhammad Ayaz; Abdulrahman Alasmari; Marzough Aziz Albalawi; Amin A. Al-Doaiss; Majed A. Bajaber; Sezai Ercisli (Algal Research, 2024)

Hyaluronic acid engineered gallic acid embedded chitosan nanoparticle as an effective delivery system for treatment of psoriasis - Afsana Sheikh; Sahim Aziz Hazari; Nagashekhara Molugulu; Saad Ali Alshehri; Shadma Wahab; Amirhossein Sahebkar; Prashant Kesharwani (Environmental Research, 2023)

Synthesis and characterization of nanobiochar from rice husk biochar for the removal of safranin and malachite green from water - Sadia Aziz; Bushra Uzair; Muhammad Ishtiaq Ali; Sundas Anbreen; Fatiha Umber; Muneeba Khalid; Alaa AA. Aljabali; Yachana Mishra; Vijay Mishra; Ángel Serrano-Aroca; Gowhar A. Naikoo; Mohamed El-Tanani; et al. (Environmental Research, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Tackling microplastics pollution in global environment through integration of applied technology, policy instruments, and legislation - Tonni Agustiono Kurniawan; Ahtisham Haider; Ayesha Mohyuddin; Rida Fatima; Muhammad Salman; Anila Shaheen; Hafiz Muhammad Ahmad; Hussein E. Al-Hazmi; Mohd Hafiz Dzarfan Othman; Faissal Aziz; Abdelkader Anouzla; Imran Ali (Journal of Environmental Management, 2023)

Shear Behaviour of Fibreglass Rock Bolts for Various Pretension Loads - Peter Gregor; Ali Mirzaghorbanali; Kevin McDougall; Naj Aziz; Behshad Jodeiri Shokri (Rock Mechanics and Rock Engineering, 2023)
In this paper, after determining an appropriate experimental design and testing scheme to test the shear performance suitably, the impacts of pretension and shear interfaces on fibreglass rock bolts were investigated. For this purpose, at the first stage, the double shear testing apparatus was modified to address the issues and shortcomings of the established testing methodology. Then, 20-tonne and 30-tonne rock bolts were tested with pretension loads of 0 kN, 10 kN, 15 kN, and 20 kN for each test scheme. For this, a 40 MPa small aggregate concrete was used for all samples to simulate the host rock. The grout used to anchor the rock bolts was mixed to the product’s recommended guidelines to ensure close resemblance to field mixtures. To maintain consistency, all samples were manufactured with the same concrete and grout recipes. The results of double shear tests revealed that increasing the pretension also increased the confining pressures at the shear interfaces for clean joints. This, in turn, reduced the damage propagating from the bolt at the shear interface and decreased the hinge point bending. The results can be applied for further analytical and numerical studies, which could utilise for a better understanding of the shear behaviour of fibreglass rock bolts.

Retraction Note: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Elucidating growth and biochemical characteristics of rice seedlings under stress from chromium VI salt and nanoparticles - Maryam Noor; Arif Ullah; Muhammad Israr Khan; Irum Raza; Muhammad Iqbal; Abdul Aziz; Gil Won Kim; Nadia Taimur; Azizullah Azizullah; Imran Ali; Pil Joo Kim (Environmental Science and Pollution Research, 2023)

Nanosheet arrays of iron oxide for enhanced ammonia synthesis via electrochemical nitrogen reduction for prospective algal membrane bioreactors - Muhammad Adnan Younis; Saira Manzoor; Amjad Ali; Fazal Haq; Tariq Aziz; Mehwish Kiran; Arshad Farid; Mohamed E. El Sayed; Mohammad N. Murshed; Zeinhom M. El-Bahy; Muhammad Saeed Akhtar (Chemosphere, 2023)

Characterization of mechanical and bonding properties of anchoring resins under elevated temperature - Hadi Nourizadeh; Ali Mirzaghorbanali; Kevin McDougall; L.H.J. Jeewantha; Peter Craig; Amin Motallebiyan; Behshad Jodeiri Shokri; Ashakan Rastegarmanesh; Naj Aziz (International Journal of Rock Mechanics and Mining Sciences, 2023)

Co-administration of Thymoquinone and Propolis in Liposomal Formulations as a Potential Approach for Treatment of Acetic Acid-Induced Ulcerative Colitis: Physiological and Histopathological Analysis - Eman Alaaeldin; Hesham Refaat; Entesar Ali Saber; Neven Makram Aziz; Nehad M. Reda Abdel-Maqsoud; Mohammed Mustafa Abd El Aleem; Maha Yehia Kamel; Fatma M. Mady (AAPS PharmSciTech, 2023)
A severe form of autoimmune-mediated inflammatory bowel disease (IBD) is termed as ulcerative colitis (UC) which ultimately results in significant mucosal damage and ulceration. Herbal remedies may be employed as an alternative for treatment of UC instead of conventional medications such as Sulfasalazine. Promising natural remedies for the treatment of IBD, including colitis, are propolis extract (PP) and thymoquinone (TQ). This study is aimed at assessing the potential of liposomal formulations of TQ and Egyptian PP in combination therapy on improving their therapeutic efficacy against ulcerative colitis in order to maximize the potential of their beneficial clinical effects. Clinical, biochemical, and histological evaluations of colonic mucosal damage and inflammation were evaluated. The results exhibited a significant increase in tissue MDA, TNFα, and nitrite levels with activation of caspase-3 in the acetic acid-induced colitis group, which is predominantly downregulated in the treatment groups. The prepared formulations of TQ and PP revealed liposomal vesicles in a nanoscale size (192 ± 20.3 and 98.2 ± 20.3 nm, respectively) and accepted stability indicated with a zeta potential of 19.3 ± 0.11 and 17.1 ± 0.25 mV, respectively. They showed an entrapment efficiency of 85.3 ± 12.6% and 69.3 ± 11.8%, respectively. At comparable doses, combination therapy with thymoquinone liposomes and propolis liposomes considerably outperformed free TQ and free PP in reducing inflammation of UC as shown in the present study by clinical, biochemical, and histological evaluations.

Integrated metabolomic analysis of Lactiplantibacillus plantarum NMGL2 reveals its survival and response to combinational cold and acidic conditions during storage of fermented milk - Hua Zhao; Urooj Ali; Qingxia Ren; Mengke Yao; Tiantian Lai; Sumaira Naz; Tariq Aziz; Manal Y. Sameeh; Min Zhang; Zhennai Yang (Food Bioscience, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Energy consumption, economic growth and Ecological footprint relationship in the top Russian energy importers: a panel data analysis - Abidin Öncel; Ali Kabasakal; Aziz Kutlar; Samet Acar (Environment, Development and Sustainability, 2023)

Phycoremediation of industrial wastewater using Vaucheria debaryana and Cladophora glomerata - Sara Khan; Amin Ullah; Tehreem Ayaz; Aamir Aziz; Komal Aman; Mudassir Habib; Semih Yilmaz; Arshad Farid; Humaira Yasmin; Qurban Ali (Environmental Monitoring and Assessment, 2023)

Temporal study of wastewater surveillance from September 2020 to March 2021: an estimation of COVID-19 patients in Lahore, Pakistan - Muhammad Adnan Ashraf; Muhammad Nawaz; Ali Asif; Muhammad Asad Ali; Adnan Mehmood; Muhammad Waqar Aziz; Muhammad Zubair Shabbir; Nadia Mukhtar; Muhammad Abu Bakr Shabbir; Sohail Raza; Tahir Yaqub (Environmental Science and Pollution Research, 2023)

Integration of geoscience data to delineate quality of the Asmari reservoir, Iranian part of the Persian Gulf basin - Aziz Abdolahi; Mohammad Bahrehvar; Ali Chehrazi; Ali Kadkhodaie; David A. Wood (Marine and Petroleum Geology, 2023)

Islamic corporate sustainability practices index aligned with SDGs towards better financial performance: Evidence from the Malaysian and Indonesian Islamic banking industry - Amin Jan; Haseeb Ur Rahman; Muhammad Zahid; Anas A. Salameh; Parvez Alam Khan; Mamdouh Abdulaziz Saleh Al-Faryan; Roslizawati Binti Che Aziz; H. Elhosiny Ali (Journal of Cleaner Production, 2023)

Potential of using jackfruit peel (Artocarpus heterophyllus) as green solution for removal of copper (II) and zinc (II) from aqueous solution: Adsorption kinetics, isotherm and thermodynamic studies - Nordiana Suhada Mohmad Tahiruddin; Rosmawati Abdul Aziz; Rosliza Ali; Nurul Izza Taib (Journal of Environmental Chemical Engineering, 2023)

Phenotypic and genotypic comparison of pathogenic group B Streptococcus isolated from human and cultured tilapia (Oreochromis species) in Malaysia - AbdulRahman Muthanna; Mohd Nasir Mohd Desa; Wardah Alsalemi; Nur Aimi Liyana Abd Aziz; Nurul Diana Dzaraly; Nurul Hana Zainal Baharin; Nur Afiza Aziz; Marlindawati Mohd Ali; Lailatul Akmar Mat Nor; Zalina Ismail; Nur Hanani Ahmad; Chua Hui Shan; et al. (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Evaluation of haematological, serum biochemical and oxidative stress parameters in cattle naturally infected with lumpy skin disease virus - Aziz Ul-Rahman; Muhammad Furqan Shahid; Muhammad Zahid Iqbal; Aijaz Ali Channa; Majeeda Rasheed; Muhammad Adnan; Rauf Mahmood; Hafiz Muhammad Ishaq; Hafeez ur Rehman Ali Khera; Kashif Hussain; Muhammad Asif Raza (Tropical Animal Health and Production, 2023)

Design, synthesis, biochemical and in silico characterization of novel naphthalene-thiourea conjugates as potential and selective inhibitors of alkaline phosphatase - Aamer Saeed; Saba Ashraf; Mubashir Aziz; Pervaiz Ali Channar; Syeda Abida Ejaz; Ammara Fayyaz; Qamar Abbas; Fatmah Ali Alasmary; Abdulnasser Mahmoud Karami; Arfa Tehzeeb; Amara Mumtaz; Hesham R. El-Seedi (Medicinal Chemistry Research, 2023)

Zinc Ortho Methyl Carbonodithioate Improved Pre and Post-Synapse Memory Impairment via SIRT1/p-JNK Pathway against Scopolamine in Adult Mice - Rifat Jahan; Mohammad Yousaf; Hamayun Khan; Shahid Ali Shah; Abdul Aziz Khan; Nousheen Bibi; Fatima Javed; Musarrat Ijaz; Arif Ali; Dong-Qing Wei (Journal of Neuroimmune Pharmacology, 2023)

Landfill leachate a new threat to water quality: a case study from the Temperate Himalayas - Shayesta Islam; Haleema Bano; Javeed Iqbal Ahmad Bhat; Malik Asif Aziz; Shahid ul Islam Bhat; Nageena Nazir; Tahir Ali; Owais Ali Wani (Environmental Monitoring and Assessment, 2023)

Seed viability, seed germination, and micropropagation of Aconitum violaceum Jacq. ex Stapf—a rare and threatened medicinal plant of Ladakh Himalaya - Abdul Hadi; Shah Rafiq; Seema Singh; Sajjad Ali; Irshad A. Nawchoo; Nasir Aziz Wagay (In Vitro Cellular & Developmental Biology - Plant, 2023)

Onion (Allium cepa) improves Nile tilapia (Oreochromis niloticus) resistance to saprolegniasis (Saprolegnia parasitica) and reduces immunosuppressive effects of cadmium - Mamdouh Y. Elgendy; Shimaa E. Ali; Mohamed Abdelsalam; Tamer H. Abd El-Aziz; Faten Abo-Aziza; Hussien A. Osman; Mohammad M. N. Authman; Wafaa T. Abbas (Aquaculture International, 2023)
The present study investigated the protective effects of dietary Allium cepa against Saprolegnia parasitica infections and the amelioration of cadmium-induced immunosuppression in Oreochromis niloticus . Saprolegnia isolates were recovered during an outbreak of saprolegniasis in farmed O. niloticus raised in a poor aquatic environment . Isolates were identified phenotypically as S. parasitica. Results were confirmed further by ITS gene sequencing. Four fish groups were kept in water with cadmium (1.5 mg/L) and fed for 30 days on a diet supplemented with crude or alcoholic extracts of A. cepa using two concentrations (0.5% or 1%). Positive (with Cd) and negative (without Cd) control fish groups were given the basal diet. The 96 h LC 50 value of Cd in tilapia was (15.1 mg/L Cd). Fish exposed to Cd showed poor growth performance parameters, abnormal biochemical measurements, impaired immunological responses, and high oxidative stress indicators. Feeding tilapia on A. cepa- supplemented diets enhanced their growth performance (WG, SGR) and improved the nonspecific immune responses (WBCs, total protein, globulins, lysozyme, myeloperoxidase, and antiproteases). The inclusion of A. cepa in the diets reduced the oxidative stress (GST, SOD) and significantly decreased fish mortality after the challenge with S. parasitica . Dietary supplementation with A. cepa reduced cadmium accumulation in fish organs and up-regulated IL-1β and IFNɣ levels. The most favorable benefits were obtained by the addition of 0.5% A. cepa extract. Our results highlight the immunostimulatory properties of A. cepa dietary supplementation for farmed tilapia and recommend its use prophylactically to control saprolegniasis and mitigate cadmium adverse effects.

Improving the physicomechanical performance of geopolymer mortars using human hair as fibers: new horizons for sustainable applications - Ayoub Aziz; Anas Driouich; Mohammed Ben Ali; Khadija Felaous; Abdelilah Bellil; Bharat Bhushan Jindal (Environmental Science and Pollution Research, 2023)

Role of silica-based porous cellulose nanocrystals in improving water absorption and mechanical properties - Tariq Aziz; Arshad Farid; Fazal Haq; Mehwish Kiran; Naveed Ullah; Shah Faisal; Amjad Ali; Farman Ullah Khan; Siming You; Awais Bokhari; Muhammad Mubashir; Lai Fatt Chuah; et al. (Environmental Research, 2023)

Potential protective effect of 3,3′-methylenebis(1-ethyl-4-hydroxyquinolin-2(1H)-one) against bleomycin-induced lung injury in male albino rat via modulation of Nrf2 pathway: biochemical, histological, and immunohistochemical study - Sara Mohamed Naguib Abdel Hafez; Entesar Ali Saber; Neven Makram Aziz; Maha Yehia Kamel; Ashraf A. Aly; El-Shimaa M. N. Abdelhafez; Manar Fouli Gaber Ibrahim (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Acute lung injury is a serious condition accounting for the majority of acute respiratory failure. Bleomycin (BLM) is an antibiotic that was first described as a chemotherapeutic agent. 3,3′-methylenebis(1-ethyl-4-hydroxyquinolin-2(1 H )-one) was reported to have anti-inflammatory, anti-apoptotic, and anti-oxidative properties. The current work aimed to assess the possible protective effects and the mechanism of protection of 3,3′-methylenebis-(1-ethyl-4-hydroxyquinolin-2(1 H )-one) on BLM-induced lung injury in addition to the effect and underlying mechanisms of nuclear factor-erythroid-related factor 2 pathway against this injury. Rats were equally divided into four groups: control group, BLM group, 1-ethyl-4-hydroxyquinolin-2(1 H )-one-treated group, and BLM with 1-ethyl-4-hydroxyquinolin-2(1 H )-one-treated group. At the end of the work, the blood samples were proceeded for biochemical study. Lung specimens were obtained for biochemical, histological, and immunohistochemical study. The results exhibited a significant increase in both malondialdehyde and tumor necrotic factor-α with a significant decrease in glutathione, superoxide dismutase, IL 10, surfactant protein A, and nuclear factor erythroid 2-related factor 2 in BLM group. The lung histological results showed various morphological changes in the form of disturbed architecture, inflammatory cell infiltration, and intraluminal debris. This group also displayed a significant increase in the mean surface area fraction of anti-cleaved caspase 3, while group IV exhibited amelioration in the previously mentioned parameters and histological alternations that were induced by BLM. It could be concluded that 3,3′-methylenebis(1-ethyl-4-hydroxyquinolin-2(1 H )-one) has anti-oxidative, anti-inflammatory, and anti-apoptotic protective effects against BLM-induced lung injury.

Microwave-assisted synthesis, spectroscopic characterization, and biological evaluation of fused thieno[2,3-d]pyrimidines as potential anti-cancer agents targeting EGFRWT and EGFRT790M - Moustafa O. Aboelez; Moumen S. Kamel; Amany Belal; Ahmed El Badry Abdel-Aziz; Mohammed A. S. Abourehab; H. Abdel-Ghany; Mohamed A. El Hamd; Mahmoud Abd El Aleem Ali El-Remaily (Molecular Diversity, 2023)

Wild food plants gathered by four cultural groups in North Waziristan, Pakistan - Noor Khalid; Lal Badshah; Adnan Ali Shah; Arman Ullah; Naushad Khan; Muhammad Abdul Aziz; Renata Sõukand; Andrea Pieroni (Genetic Resources and Crop Evolution, 2023)

Estimating atmospheric radon deviation using statistical coefficients: Sulaymaniyah city, Iraq, as a case of study - Adil M. Hussein; Kamal O. Abdullah; Aziz H. Fattah; Ranjdar R. Mohammed-Ali (Isotopes in Environmental and Health Studies, 2023)

CuO improved energy band of AgO/fibrous SiO2–ZrO2 for optimized simultaneous photocatalytic redox of chromium (VI) and p-cresol using response surface methodology - F.F.A. Aziz; A.A. Jalil; N.S. Hassan; A.A. Fauzi; N.F. Khusnun; M.W. Ali; M.B. Bahari; W. Nabgan (Environmental Research, 2023)

Identification and modeling of the hydrocarbon-bearing Ghar sand using seismic attributes, wireline logs and core information, a case study on Asmari Formation in Hendijan Field, southwest part of Iran - Aziz Abdolahi; Ali Chehrazi; Ali Kadkhodaie; Seyedmohsen Seyedali (Modeling Earth Systems and Environment, 2023)

The versatility of nanocellulose, modification strategies, and its current progress in wastewater treatment and environmental remediation - Ajmal Shahzad; Muhammad Wajid Ullah; Jawad Ali; Kazim Aziz; Muhammad Asif Javed; Zhijun Shi; Sehrish Manan; Mazhar Ul-Islam; Mudasir Nazar; Guang Yang (Science of The Total Environment, 2023)

Gastroprotective and anti-Helicobacter pylori potentials of essential oils from the oleoresins of Araucaria bidwillii and Araucaria heterophylla - Dalia E. Ali; Marwa M. Abd el-Aziz; Sherihan Salaheldin Abdelhamid Ibrahim; Eman Sheta; Essam Abdel-Sattar (Inflammopharmacology, 2023)
Plant resins or oleoresins comprise a chemically complex mixture of different classes of compounds. Oleoresin of the genus Araucaria combines essential oil (EO) and resin. It possesses gastroprotective, cytotoxic, and timicrobial, antipyretic, and anti-inflammatory activities. The study aimed to investigate the EOs from the oleoresins of two Araucaria species, A. bidwillii and A. heterophylla, chemically and biologically for their gastroprotective, anti-inflammatory, antioxidant, and anti- Helicobacter pylori potentials. The chemical composition of both species cultivated in Egypt was analyzed with GC-MS and compared with those cultivated abroad using principal component analysis (PCA). There were 37 and 17 secondary metabolites identified in A. heterophylla and A. bidwillii , respectively. The EOs of both species showed a pronounced inhibitory effect on Helicobacter pylori activity in vitro. The gastroprotective effect was assessed in vivo using ethanol-induced gastric ulcer model in rats. Inflammatory cytokines, oxidative stress, and the nuclear factor-kappa B (NF-κB) biomarkers were assessed in the stomach tissues. The ulcer index and percentage of ulcer protection were determined. Stomach sections were examined histopathologically by staining with (H/E) and periodic acid Schiff (PAS). Moreover, the proliferative index was determined using the Ki-67 immunostaining. The treatment of rats with EOs (50, 100, and 200 mg/kg, orally) 1 hour prior to ethanol administration showed promising gastroprotective, anti-inflammatory, and antioxidant potentials. These findings declared the gastroprotective role played by both EOs with the superiority of A. bidwillii over A. heterophylla via modulation of oxidative stress/NF-κB/inflammatory cytokines. Their use can be recommended to protect against the recurrence of peptic ulcers.

Impact of natural resource rents and economic growth on environmental degradation in the context of COP-26: Evidence from low-income, middle-income, and high-income Asian countries - Jing Luo; Syed Ahtsham Ali; Babar Aziz; Ahmed Aljarba; Hatem Akeel; Imran Hanif (Resources Policy, 2023)

Biomonitoring of mercury in water, sediments, and fish (brown and rainbow trout) from remote alpine lakes located in the Himalayas, Pakistan - Javed Nawab; Junaid Ghani; Syed Aziz Ur Rehman; Muhammad Idress; Muhammad Luqman; Sardar Khan; Ali Asghar; Ziaur Rahman (Environmental Science and Pollution Research, 2022)

Axial Performance of Cementitious Grouted Cable Bolts Under Rotation Constraint Scenarios - Ashkan Rastegarmanesh; Ali Mirzaghorbanali; Kevin McDougall; Naj Aziz; Sina Anzanpour; Hadi Nourizadeh; Mahdi Moosavi (Rock Mechanics and Rock Engineering, 2022)
With the increased use of cable bolts in mining and civil projects worldwide, it is important to understanding the performance of these support structures in different scenarios. The axial load transfer mechanisms of six cable bolts were investigated experimentally in this research study. A large-scale pull-out testing apparatus with a capacity of 1000 kN was designed and manufactured as part of the investigation. A common commercial cementitious grout with a uniaxial compressive strength of 60 MPa was used to encapsulate 300 mm length samples. Passive confinement encapsulated each sample to ensure the concrete’s integrity during the testing. The encapsulated cable bolts were then subjected to axial loads using a hydraulic ram, with the axial load and displacement measured using a load cell and LVDTs. Two scenarios were investigated: free rotation and restricted rotation. The results demonstrated that the apparatus effectively recorded the behaviour of the cable during pull-out and identified that the radial stiffness of the samples had a significant impact on the overall load of the system. The results also indicated that rotation had a limited influence on the load behaviour of the samples tested.

Combination Therapy of Stem Cell-derived Exosomes and Biomaterials in the Wound Healing - Ali Golchin; Forough Shams; Arefeh Basiri; Parviz Ranjbarvan; Samaneh Kiani; Roya Sarkhosh-Inanlou; Abdolreza Ardeshirylajimi; Shiva Gholizadeh-Ghaleh Aziz; Sanaz Sadigh; Yousef Rasmi (Stem Cell Reviews and Reports, 2022)

Sustainability and mechanical property assessment of concrete incorporating eggshell powder and silica fume as binary and ternary cementitious materials - Samiullah Sohu; Naraindas Bheel; Ashfaque Ahmed Jhatial; Abdul Aziz Ansari; Irfan Ali Shar (Environmental Science and Pollution Research, 2022)

The nexus between traditional foraging and its sustainability: a qualitative assessment among a few selected Eurasian case studies - Muhammad Abdul Aziz; Giulia Mattalia; Naji Sulaiman; Adnan Ali Shah; Zbynek Polesny; Raivo Kalle; Renata Sõukand; Andrea Pieroni (Environment, Development and Sustainability, 2022)

Analysis and farmers’ perception of climate change in the Kashmir Valley, India - S. Sheraz Mahdi; B. S. Dhekale; Rukhsana Jan; M. Anwar Bhat; Ashaq Hussain; Intikhab Aalum Jehangir; Najeebul Rehman Sofi; Latief Ahmed; Asif M. Iqbal Qureshi; Aziz Mujtaba Aezum; Shabir A. Bangroo; Owais Ali Wani; et al. (Theoretical and Applied Climatology, 2022)

Angle Shear Testing of 15.2 mm Seven Wire Cable Bolt - Naj Aziz; Ali Mirzaghorbanali; Sina Anzanpour; Ashkan Rastegarmanesh; Saman Khaleghparat; Jan Nemcik; Joung Oh; Guangyao Si (Rock Mechanics and Rock Engineering, 2022)
This paper focuses on the experimental study of shear testing of 15.2 mm, 25 t capacity seven wire cables at zero, 30° and 45° angles using two different shear testing facilities at the University of Wollongong (UOW) and the University of Southern Queensland (USQ) in Toowoomba. A circular double-shear rig MK-IV was used for testing cable perpendicular to the sheared joint faces (zero angle of orientation), while testing the cable at 30° and 45° was carried out using a larger-size rectangular-shaped rig. Testing was carried out based on the double-shear testing methodology wherein cable bolts were fully encapsulated using Stratabinder HS inside of three concrete blocks representing host rocks. This study was part of the tri-universities-funded ACARP project C27040 awarded jointly to the University of New South Wales, University of Wollongong and University of Southern Queensland. The objective of the experimental testing programme was to provide the essential information for the development of numerical models that included not only the technical parameters, but also the behavioural outcomes from various tests with respect to the angles of testing and their effect on the nature of cable failure, be it pure shear, tensile shear or shear tensile, cable pretension and the credibility of the effectiveness of the Barrel and Wedge (B&W) anchorage system were evaluated. Laboratory facilities at both UOW and USQ were used in the study. The prepared double-shear samples were then positioned inside of compression testing machines and were subjected to shear testing. The values of shear load and displacement were recorded for various inclinations angles. It was found that increased angle of shear contributes to increased stiffness of the cable in shear with other parameters being equal. Subroutine codes were developed in UDEC and 3DEC to simulate shear behaviour of cable bolts installed in angles for different pretension loads. The numerical simulations indicated that UDEC and 3DEC can simulate the general shear behaviour of cable bolts reasonably well for various inclination angles and pretension values.

The diagnostic accuracy of intraoperative frozen section biopsy for diagnosis of sentinel lymph node metastasis in breast cancer patients: a meta-analysis - Alaa Ahmed Elshanbary; Alaa Abdelsameia Awad; Alaa Abdelsalam; Islam H. Ibrahim; Walid Abdel-Aziz; Youssef Bahaaeldin Darwish; Alaa Saad Isa; Boutheyna Drid; Marwa Gamal Mustafa; Radwa Hamdy Allam; Amira A. Abo Ali; Anas Zakarya Nourelden; et al. (Environmental Science and Pollution Research, 2022)
Sentinel lymph node (SLN) sampling is important for evaluating the nodal stage of breast cancer when the axillary nodes are clinically free of metastasis. The intraoperative frozen section (IFS) of SLN is used for lymph node assessment. This meta-analysis aims to provide evidence about the diagnostic accuracy and the applicability of IFS of SLN in breast cancer patients. Data were collected by searching PubMed, Cochrane, Scopus, and Web of Science electronic databases for trials matching our eligibility criteria. The statistical analysis included the sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and pooled studies’ diagnostic odds ratio outcomes. The analyses were conducted using the Open Meta-analyst software. This meta-analysis pooled the results of 110 studies. The overall sensitivity of IFS for SLN metastasis was 74.7%; 95% CI [72.0, 77.2], P < 0.001. It was 31.4% 95% CI [25.2, 38.3], P < 0.001 for the micro-metastasis, and 90.2%; 95% CI [86.5, 93.0], P < 0.001 for the macro-metastasis. The overall specificity was 99.4%; 95% CI [99.2, 99.6], P < 0.001. The overall positive likelihood ratio was 121.4; 95% CI [87.9, 167.6], P < 0.001, and the overall negative likelihood ratio was 0.226; 95% CI [0.186, 0.274], P < 0.001. The overall diagnostic odds ratio of IFS for diagnosing SLN metastasis was 569.5; 95% CI [404.2, 802.4], P < 0.001. The intraoperative frozen section of SLN has good sensitivity for diagnosing breast cancer macro-metastasis. However, the sensitivity is low for micro-metastasis. The specificity is very satisfactory.

Correction to: An Integrated Geoproduct Development for Geotourism in Langkawi UNESCO Global Geopark: a Case Study of the Kubang Badak Biogeotrail - Ibrahim Komoo; Norzaini Azman; Norhayati Ahmad; Che Aziz Ali; Azmil Munif Mohd Bukhari (Geoheritage, 2022)

Exploring environment sensitivity to fiscal and monetary policies in China: using ecological footprints as a contemporary proxy - Usman Saleem Yousaf; Farhan Ali; Shabib Haider Syed; Babar Aziz; Saima Sarwar (Environmental Science and Pollution Research, 2022)

What causes environmental degradation in Pakistan? Embossing the role of fossil fuel energy consumption in the view of ecological footprint - Usman Saleem Yousaf; Farhan Ali; Babar Aziz; Saima Sarwar (Environmental Science and Pollution Research, 2022)

Strengthening of high plastic clays by geotextile reinforcement - Muhammad Hamza; Mubashir Aziz; Wang Xiang; Muhammad Waqas Younis; Zhihong Nie; Muhammad Ali; Mudassar Dilawar; Ashiru Mohammed; Farhad Ali; Rahat Ullah; Mazhar Yasin; Atteq Ur Rehman (Arabian Journal of Geosciences, 2022)

An Integrated Geoproduct Development for Geotourism in Langkawi UNESCO Global Geopark: a Case Study of the Kubang Badak Biogeotrail - Ibrahim Komoo; Norzaini Azman; Norhayati Ahmad; Che Aziz Ali; Azmil Munif Mohd Bukhari (Geoheritage, 2022)

Role of pine wilt disease based on optimal control strategy at multiple scales: A case study of Korea - Muhammad Ozair; Takasar Hussain; Kashif Ali Abro; Sajid Jameel; Aziz Ullah Awan (Journal of Biosciences, 2021)

Short and long-run causal effects of agriculture, forestry, and other land use on greenhouse gas emissions: evidence from China using VECM approach - Ruishi Si; Noshaba Aziz; Ali Raza (Environmental Science and Pollution Research, 2021)

Simultaneous remediation of hexavalent chromium and organic pollutants in wastewater using period 4 transition metal oxide-based photocatalysts: a review - N. M. Izzudin; A. A. Jalil; F. F. A. Aziz; M. S. Azami; M. W. Ali; N. S. Hassan; A. F. A. Rahman; A. A. Fauzi; D. V. N. Vo (Environmental Chemistry Letters, 2021)

Correction to: Health risk assessment of hexachlorocyclohexane in soil, water and plants in the agricultural area of Potohar region, Punjab, Pakistan - Talat Ara; Waqar-Un Nisa; Rukhsanda Aziz; Muhammad Tariq Rafiq; Rafaqat Ali Gill; Malik Tahir Hayat; Uzma Afridi (Environmental Geochemistry and Health, 2021)

Role of multidrug resistance-associated proteins in cancer therapeutics: past, present, and future perspectives - Ahmed Elfadadny; Hussein M. El-Husseiny; Amira Abugomaa; Rokaia F. Ragab; Eman A. Mady; Mohamed Aboubakr; Haney Samir; Ahmed S. Mandour; Amany El-Mleeh; Ali H. El-Far; Ayman H. Abd El-Aziz; Mohamed Elbadawy (Environmental Science and Pollution Research, 2021)

Performance of Horizontal Roughing Filter for Colour Removal of Palm Oil Mill Effluent Using Natural Adsorbent - Arezoo Fereidonian Dashti; Hamidi Abdul Aziz; Mohd Nordin Adlan; Ali Huddin Ibrahim (Environmental Processes, 2021)

Health risk assessment of hexachlorocyclohexane in soil, water and plants in the agricultural area of Potohar region, Punjab, Pakistan - Talat Ara; Waqar-Un Nisa; Rukhsanda Aziz; Muhammad Tariq Rafiq; Rafaqat Ali Gill; Malik Tahir Hayat; Uzma Afridi (Environmental Geochemistry and Health, 2021)

An in vitro antiviral activity of iodine complexes against SARS-CoV-2 - Imran Altaf; Muhammad Faisal Nadeem; Nadir Hussain; Muhammad Nawaz; Sohail Raza; Muhammad Abu bakr Shabbir; Muhammad Adnan Ashraf; Muhammad Asad Ali; Sohail Hassan; Muhammad Waqar Aziz; Nazish Matti; Muhammad Ashraf; et al. (Archives of Microbiology, 2021)

RETRACTED ARTICLE: Inhibition of NF-κB signaling and HSP70/HSP90 proteins by newly synthesized hydrazide derivatives in arthritis model - Ashraf Ullah Khan; Amna Khan; Adnan Khan; Bushra Shal; Abdul Aziz; Muhammad Naeem Ahmed; Salman Ul Islam; Hussain Ali; Adeeb Shehzad; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Effect of Organic Amendment on Soil Fertility, Mineral Nutrition, and Yield of Majhoul Date Palm Cultivar in Drâa-Tafilalet Region, Morocco - Mohamed Ou-Zine; Sarah Symanczik; Fouad Rachidi; Mustapha Fagroud; Larbi Aziz; Ali Abidar; Paul Mäder; El Hassan Achbani; Abdellatif Haggoud; Mustapha Abdellaoui; Rachid Bouamri (Journal of Soil Science and Plant Nutrition, 2021)

Drought Tolerance Strategies in Plants: A Mechanistic Approach - Muhammad Ilyas; Mohammad Nisar; Nadeem Khan; Ali Hazrat; Aamir Hamid Khan; Kashif Hayat; Shah Fahad; Aziz Khan; Abid Ullah (Journal of Plant Growth Regulation, 2021)

The Feasibility of Monoculture and Polyculture of Striped Catfish and Nile Tilapia in Different Proportions and Their Effects on Growth Performance, Productivity, and Financial Revenue - Abdallah Tageldein Mansour; Belal Wagih Allam; Tarek Mohamed Srour; Eglal Ali Omar; Abdel Aziz Mousa Nour; Hala Saber Khalil (Journal of Marine Science and Engineering, 2021)
Cultivation of species of high growth rates is a key achievement of sustainable aquaculture development, with the aim of increasing animal protein per capita, maintaining food security and preserving freshwater usage. The present study was conducted to evaluate the feasibility of monoculture and polyculture of striped catfish, Pangasianodon hypophthalmus, and Nile tilapia, Oreochromis niloticus, in different proportions and their effect on growth performance, survival, productivity, feed utilization, body composition, and financial revenue. Five experimental treatments were designed as follows: monoculture of striped catfish (100%), Nile tilapia (100%) and polyculture in different proportions of striped catfish and Nile tilapia (25%:75%; 50%:50%; 75%:25%, respectively), each in three replicates. The fish feeding regime consisted of isonitrogenous (307.80 g kg−1) and isocaloric (19.27 kJ g−1) diets for 14 weeks. The results revealed that the highest growth performance, feed utilization, survival of striped catfish were obtained in monoculture, followed by polyculture of striped catfish and Nile tilapia (in low proportions) (75%:25%). The total production per m3 reached 5.41 kg m−3 in the monoculture of striped catfish, this production decreased in polyculture by 52%, 46% and 23% with 25%; 50%; 75% of striped catfish. The gross margin significantly increased, in case of striped catfish farmed in monoculture, compared to other polyculture proportions. While the gross margin per m−3 of water was 6, 0.5, 1 and 3 $ in monoculture and different polyculture proportions, respectively. Moreover, the feed cost per kilogram of protein gain significantly decreased in the monoculture of striped catfish compared to other polyculture treatments. The growth performance and survival of tilapia showed no significant difference among different treatments. In addition, the proximate chemical composition did not differ in respect to species in different studied treatments. Monoculture of striped catfish is recommended to achieve high production and improve financial revenue per water unit (m−3), for better sustainable development of aquaculture.

First report of Pseudocercospora fuligena in tomato greenhouses in Turkey - Esra Gül; Aziz Karakaya; Ali Ergül (Journal of Plant Pathology, 2021)

Lumpy skin disease in Kazakhstan - Mukhit B. Orynbayev; Raikhan K. Nissanova; Berik M. Khairullin; Arman Issimov; Kunsulu D. Zakarya; Kulyaisan T. Sultankulova; Lespek B. Kutumbetov; Ali B. Tulendibayev; Balzhan Sh. Myrzakhmetova; Erbol D. Burashev; Sergazy S. Nurabayev; Olga V. Chervyakova; et al. (Tropical Animal Health and Production, 2021)
This study describes the registration of the first cases of lumpy skin disease in July 2016 in the Republic of Kazakhstan. In the rural district of Makash, Kurmangazinsky district of Atyrau region, 459 cattle fell ill and 34 died (morbidity 12.9% and mortality 0.96%). To determine the cause of the disease, samples were taken from sick and dead animals, as well as from insects and ticks. LSDV DNA was detected by PCR in all samples from dead animals and ticks (Dermacentor marginatus and Hyalomma asiaticum), in 14.29% of samples from horseflies (Tabanus bromius), and in one of the samples from two Stomoxys calcitrans flies. The reproductive LSD virus was isolated from organs of dead cattle and insects in the culture of LT and MDBK cells. The virus accumulated in cell cultures of LT and MDBK at the level of the third passage with titers in the range of 5.5–5.75 log 10 TCID50/cm 3 . Sequencing of the GPCR gene allowed us to identify this virus as a lumpy skin disease virus.

Foliage applied potassium improves stay green, photosynthesis and yield of maize (Zea mays L.) under rainfed condition - Allah Wasaya; Tauqeer Ahmad Yasir; Naeem Sarwar; Omer Farooq; Atique ur Rehman; Khuram Mubeen; Muqarrab Ali; Muhammad Affan; Ahsan Aziz (Plant Physiology Reports, 2021)

Depositional, diagenetic, and sequence stratigraphic constrains on reservoir characterization: a case study of middle Jurassic Samana Suk Formation, western Salt Range, Pakistan - Bilal Wadood; Mansoor Aziz; Junaid Ali; Nasar Khan; Jamal Wadood; Ahmad Khan; Muhammad Shafiq; Mohib Ullah (Journal of Sedimentary Environments, 2021)

A Probabilistic Model to Determine Main Caving Span by Evaluating Cavability of Immediate Roof Strata in Longwall Mining - Sadjad Mohammadi; Mohammad Ataei; Reza Kakaie; Ali Mirzaghorbanali; Naj Aziz (Geotechnical and Geological Engineering, 2021)

The role of natural resources, globalization, and renewable energy in testing the EKC hypothesis in MINT countries: new evidence from Method of Moments Quantile Regression approach - Noshaba Aziz; Arshian Sharif; Ali Raza; Kittisak Jermsittiparsert (Environmental Science and Pollution Research, 2021)

Histological and Physiological Studies of the Effect of Bone Marrow-Derived Mesenchymal Stem Cells on Bleomycin Induced Lung Fibrosis in Adult Albino Rats - Dina Mohamed Zakaria; Noha Mahmoud Zahran; Samia Abdel Aziz Arafa; Radwa Ali Mehanna; Rehab Ahmed Abdel-Moneim (Tissue Engineering and Regenerative Medicine, 2021)

Carbon, nitrogen, and phosphorus stoichiometry mediate sensitivity of carbon stabilization mechanisms along with surface layers of a Mollisol after long-term fertilization in Northeast China - Muhammad Mohsin Abrar; Hu Xu; Tariq Aziz; Nan Sun; Adnan Mustafa; Muhammad Wajahat Aslam; Syed Atizaz Ali Shah; Khalid Mehmood; Baoku Zhou; Xingzhu Ma; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2021)

Advanced microbial fuel cell for waste water treatment—a review - Abdul Sattar Jatoi; Faheem Akhter; Shaukat Ali Mazari; Nizamuddin Sabzoi; Shaheen Aziz; Suhail Ahmed Soomro; Nabisab Mujawar Mubarak; Humair Baloch; Abdul Qayoom Memon; Shoaib Ahmed (Environmental Science and Pollution Research, 2021)

Removal of azo dye from aqueous solution by a low-cost activated carbon prepared from coal: adsorption kinetics, isotherms study, and DFT simulation - Saeed Ullah Jan; Aziz Ahmad; Adnan Ali Khan; Saad Melhi; Iftikhar Ahmad; Guohua Sun; Cheng-Meng Chen; Rashid Ahmad (Environmental Science and Pollution Research, 2021)

Impacts of albedo and atmospheric conditions on the efficiency of solar energy: a case study in temperate climate of Choman, Iraq - Ali Saleh Aziz; Mohammad Faridun Naim Tajuddin; Mohd Rafi Adzman; Makbul A. M. Ramli (Environment, Development and Sustainability, 2021)

Removal of contaminant metformin from water by using Ficus benjamina zero-valent iron/copper nanoparticles - Hossam Mohammed Abd El-Aziz; Rabie Saad Farag; Soha Ali Abdel-Gawad (Nanotechnology for Environmental Engineering, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Efficacy of Nanofertilizer, Fulvic Acid and Boron Fertilizer on Sugar Beet (Beta vulgaris L.) Yield and Quality - Essam E. Kandil; Nader R. Abdelsalam; Ashraf A. Abd EL Aziz; Hayssam M. Ali; Manzer H. Siddiqui (Sugar Tech, 2020)

Phylogenetic Analysis and Structural Perspectives of RNA-Dependent RNA-Polymerase Inhibition from SARs-CoV-2 with Natural Products - Abbas Khan; Mazhar Khan; Shoaib Saleem; Zainib Babar; Arif Ali; Abdul Aziz Khan; Zain Sardar; Fahad Hamayun; Syed Shujait Ali; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Response surface methodology and artificial neural network for remediation of acid orange 7 using TiO2-P25: optimization and modeling approach - Muhammad Zulfiqar; Sujan Chowdhury; Abdul Aziz Omar; Ahmer Ali Siyal; Suriati Sufian (Environmental Science and Pollution Research, 2020)

Enhanced bioremediation of diesel range hydrocarbons in soil using biochar made from organic wastes - Sadia Aziz; Muhammad Ishtiaq Ali; Uzma Farooq; Asif Jamal; Fang-Jing Liu; Huan He; Hongguang Guo; Michael Urynowicz; Zaixing Huang (Environmental Monitoring and Assessment, 2020)

Suspended Solid Removal of Palm Oil Mill Effluent Using Horizontal Roughing Filter and Calcinated Limestone - Arezoo Fereidonian Dashti; Hamidi Abdul Aziz; Ali Huddin Ibrahim; Mohammad Ali Zahed (Water, Air, & Soil Pollution, 2020)

Correction to: MicroRNA signature in hepatocellular carcinoma patients: identification of potential markers - Mohammed Elhendawy; Enas A. Abdul-Baki; Sherief Abd-Elsalam; Maha M. Hagras; Abdul-Aziz Zidan; Amira Y. Abdel-Naby; Mona Watany; Ibrahem Ali Elkabash; Mohamed Labib Salem; Mohamed Elshanshoury; Shaimaa Soliman; Said Abdou (Molecular Biology Reports, 2020)

MicroRNA signature in hepatocellular carcinoma patients: identification of potential markers - Mohammed Elhendawy; Enas A. Abdul-Baki; Sherief Abd-Elsalam; Maha M. Hagras; Abdul-Aziz Zidan; Amira Y. Abdel-Naby; Mona Watny; Ibrahem Ali Elkabash; Mohamed Labib Salem; Mohamed Elshanshoury; Shaimaa Soliman; Said Abdou (Molecular Biology Reports, 2020)

Photocatalytic degradation of methyl orange from wastewater using a newly developed Fe-Cu-Zn-ZSM-5 catalyst - Mushtaq Ahmad; Abdul Raman Abdul Aziz; Shaukat Ali Mazari; Abdul Ghaffar Baloch; Sabzoi Nizamuddin (Environmental Science and Pollution Research, 2020)

Characterization of Biosynthesized Silver Nanoparticles Using Lactobacillus rhamnosus GG and its In Vitro Assessment Against Colorectal Cancer Cells - Seyed Mohammad Ali Aziz Mousavi; Seyed Ali Mirhosseini; Mona Rastegar Shariat Panahi; Hamideh Mahmoodzadeh Hosseini (Probiotics and Antimicrobial Proteins, 2020)

An Integrated Systems Biology and Network-Based Approaches to Identify Novel Biomarkers in Breast Cancer Cell Lines Using Gene Expression Data - Abbas Khan; Zainab Rehman; Huma Farooque Hashmi; Abdul Aziz Khan; Muhammad Junaid; Abrar Mohammad Sayaf; Syed Shujait Ali; Fakhr Ul Hassan; Wang Heng; Dong-Qing Wei (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Effect of biochars, biogenic, and inorganic amendments on dissolution and kinetic release of phytoavailable silicon in texturally different soils under submerged conditions - Muhammad Irfan Sohail; Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Ashar Ayub; Tariq Aziz; Muhammad Saqib; Ghulam Murtaza (Arabian Journal of Geosciences, 2020)

Estimation of Semiarid Forest Canopy Cover Using Optimal Field Sampling and Satellite Data with Machine Learning Algorithms - Ali Mahdavi; Jalal Aziz (Journal of the Indian Society of Remote Sensing, 2020)

Impacts of slurry and dry forms of low-rank coal (lignite) on quality of syngas produced - Imran Nazir Unar; Ghulamullah Maitlo; Suhail Ahmed Soomro; Shaheen Aziz; Syed Abdul Karim Shah; Rasool Bux Mahar; Zulfiqar Ali Bhatti; Mohammad Safar Korai (Clean Technologies and Environmental Policy, 2020)

Characterization of a novel cotton MYB gene, GhMYB108-like responsive to abiotic stresses - Abid Ullah; Muhammad Tahir Ul Qamar; Mohammad Nisar; Ali Hazrat; Gul Rahim; Aamir Hamid Khan; Kashif Hayat; Saeed Ahmed; Waqar Ali; Aziz khan; Xiyan Yang (Molecular Biology Reports, 2020)

Revisiting the role of forestry, agriculture, and renewable energy in testing environment Kuznets curve in Pakistan: evidence from Quantile ARDL approach - Noshaba Aziz; Arshian Sharif; Ali Raza; Kong Rong (Environmental Science and Pollution Research, 2020)

Lipids as biomarkers of brain disorders - Ghulam Hussain; Haseeb Anwar; Azhar Rasul; Ali Imran; Muhammad Qasim; Shamaila Zafar; Muhammad Imran; Syed Kashif Shahid Kamran; Nimra Aziz; Aroona Razzaq; Waseem Ahmad; Asghar Shabbir; et al. (Critical Reviews in Food Science and Nutrition, 2020)

Hepatoprotective role of berberine against paraquat-induced liver toxicity in rat - Aziz Eftekhari; Amir Hasanzadeh; Rovshan Khalilov; Hasan Hosainzadegan; Elham Ahmadian; Mohammad Ali Eghbal (Environmental Science and Pollution Research, 2020)

Response of growth, antioxidant enzymes and root exudates production towards As stress in Pteris vittata and in Astragalus sinicus colonized by arbuscular mycorrhizal fungi - Liu Yizhu; Muhammad Imtiaz; Allah Ditta; Muhammad Shahid Rizwan; Muhammad Ashraf; Sajid Mehmood; Omar Aziz; Fathia Mubeen; Muhammad Ali; Nosheen Noor Elahi; Raina Ijaz; Sha Lele; et al. (Environmental Science and Pollution Research, 2020)

Detection of QTLs for outcrossing-related traits in rice (Oryza sativa L.) by association mapping and the RSTEP-LRT method - Lal Bux; Dalu Li; Muhammad Faheem; Ognigamal Sowadan; Zhiyao Dong; Erbao Liu; Mehtab Ali; Yanhui Li; Helder Manuel Sitoe; Abdul Aziz Mirani; Delin Hong (Euphytica, 2019)

Circulation of multiple subtypes (A, G and CRFs 02_AG) of human immunodeficiency virus type 1 (HIV-1) in selected districts of Punjab province, Pakistan - Saima Yaqub; Tahir Yaqub; Muhammad Zubair Shabbir; Asif Nadeem; Nadia Mukhtar; Firnas Ata Ur Rehman; Aziz-ul Rahman; Muhammad Furqan Shahid; Muzaffar Ali; Tayyebah Sohail; Zarfishan Tahir (Archives of Virology, 2019)

Carbamazepine Removal from Aqueous Solution by Green Synthesis Zero-Valent Iron/Cu Nanoparticles with Ficus Benjamina Leaves’ Extract - Hossam Mohammed Abdel-Aziz; Rabie Saad Farag; Soha Ali Abdel-Gawad (International Journal of Environmental Research, 2019)

Occurrences and characterisation of textural and mineralogical heterogeneities in analogue reservoir sandstones: case study of the onshore Central Sarawak, NW Borneo - Ekundayo Joseph Adepehin; Che Aziz Ali; Abdullah Adli Zakaria; Olabode Modupe Bankole (Arabian Journal of Geosciences, 2019)

Distribution and origin of iron and manganese in groundwater: case study, Balat-Teneida area, El-Dakhla Basin, Egypt - Hassan Khozyem; Ali Hamdan; Abdel Aziz Tantawy; Ashraf Emam; Eman Elbadry (Arabian Journal of Geosciences, 2019)

Responses of pro-inflammatory cytokines, acute phase proteins and cytological analysis in serum and cerebrospinal fluid during haemorrhagic septicaemia infection in buffaloes - Eric Lim Teik Chung; Faez Firdaus Abdullah Jesse; Ali Dhiaa Marza; Hayder Hamzah Ibrahim; Yusuf Abba; Mohd Zamri-Saad; Abdul Wahid Haron; Mohd Azmi Mohd Lila; Abdul Aziz Saharee; Abdul Rahman Omar; Md Zuki Abu Bakar; Mohd Jefri Norsidin (Tropical Animal Health and Production, 2019)

Impacts of Egyptian propolis extract on rat cerebellum intoxicated by aluminum silicate: histopathological studies - Nahed A. Omar; Ali H. Abu-Almaaty; Yasmin M. Abd El-Aziz; Ahmed M. Abdeen; Fatma El Zahraa Ammar Mohamed; Mohamed M. M. Hashem; Seddik Hammad (Environmental Science and Pollution Research, 2019)

Pixel-Based Classification of Hyperspectral Images Using Convolutional Neural Networks - Syed Aamer Hussain; Ali Tahir; Junaid Aziz Khan; Ahmad Salman (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2019)

Adsorption and in vitro release study of curcumin form polyethyleneglycol functionalized multi walled carbon nanotube: kinetic and isotherm study - Somayeh Koupaei Malek; Mohammad Ali Gabris; Binta Hadi Jume; Raheleh Baradaran; Madzlan Aziz; Khairil Juhanni Bt. Abd Karim; Hamid Rashidi Nodeh (DARU Journal of Pharmaceutical Sciences, 2019)

Fluoride in Iranian Drinking Water Resources: a Systematic Review, Meta-analysis and Non-carcinogenic Risk Assessment - Hassan Keramati; Ali Miri; Mehdi Baghaei; Aziz Rahimizadeh; Raheb Ghorbani; Yadolah Fakhri; Abotaleb Bay; Masoud Moradi; Zohreh Bahmani; Mansour Ghaderpoori; Amin Mousavi Khaneghah (Biological Trace Element Research, 2019)

New insights into the structure of the South Caspian Basin from seismic reflection data, Gorgan Plain, Iran - Ali Radfar; Aziz Rahimi Chakdel; Ali Nejati; Mehrdad Soleimani; FaridTaati (International Journal of Earth Sciences, 2019)

Monogenic, Polygenic, and MicroRNA Markers for Ischemic Stroke - Wu Chen; Bharati Sinha; Yi Li; Larry Benowitz; Qinhua Chen; Zhenghong Zhang; Nirav J. Patel; Ali M. Aziz-Sultan; Antonio E. Chiocca; Xin Wang (Molecular Neurobiology, 2019)

Effect of poultry litter biochar on chromium (Cr) bioavailability and accumulation in spinach (Spinacia oleracea) grown in Cr-polluted soil - Adiba Khan Sehrish; Rukhsanda Aziz; Muhammad Mazhar Hussain; Muhammad Tariq Rafiq; Muhammad Rizwan; Niaz Muhammad; Muhammad Khalid Rafiq; Anum Sehar; Jalal ud Din; Mohammad I. Al-Wabel; Shafaqat Ali (Arabian Journal of Geosciences, 2019)

Optimization of β-Carotene Production from Rhodotorula glutinis ATCC 4054 Growing on Agro-industrial Substrate Using Plackett–Burman Design - Sherif M. Husseiny; Ahmed A. Abdelhafez; Ali Abdel-Aziz Ali; Hala Mohamed Sand (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Antiproliferative, antioxidant and binding mechanism analysis of prodigiosin from newly isolated radio-resistant Streptomyces sp. strain WMA-LM31 - Wasim Sajjad; Sajjad Ahmad; Iffat Aziz; Syed Sikander Azam; Fariha Hasan; Aamer Ali Shah (Molecular Biology Reports, 2018)

Seismic based characterization of total organic content from the marine Sembar shale, Lower Indus Basin, Pakistan - Omer Aziz; Tahir Hussain; Matee Ullah; Asher Samuel Bhatti; Aamir Ali (Marine Geophysical Research, 2018)

Dietary propionic acid enhances antibacterial and immunomodulatory effects of oxytetracycline on Nile tilapia, Oreochromis niloticus - Mohammed El-Adawy; Magdy Abd El-Aziz; Kamal El-Shazly; Nadia G. Ali; Mohammed Abu El-Magd (Environmental Science and Pollution Research, 2018)

Biochar for sustainable soil and environment: a comprehensive review - Niaz Muhammad; Mubashir Hussain; Waheed Ullah; Taj Ali Khan; Shafaqat Ali; Ali Akbar; Rukhsanda Aziz; Muhammad Khalid Rafiq; Robert Thomas Bachmann; Mohammad I. Al-Wabel; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

Synthesis of biochar from sugarcane filter-cake and its impacts on physiological performance of lettuce (Lettuce sativa) grown on cadmium contaminated soil - Anum Sehar; Rukhsanda Aziz; Muhammad Tariq Rafiq; Muhammad Mazhar Hussain; Muhammad Rizwan; Adiba Khan Sehrish; Muhammad Khalid Rafiq; Jalal ud Din; Qaiser Hussain; Mohammad I. Al-Wabel; Shafaqat Ali (Arabian Journal of Geosciences, 2018)

An Experimental Study on the Shear Performance of Fully Encapsulated Cable Bolts in Single Shear Test - Naj Aziz; Haleh Rasekh; Ali Mirzaghorbanali; Guanyu Yang; Saman Khaleghparast; Jan Nemcik (Rock Mechanics and Rock Engineering, 2018)

Radiation efficiency and nitrogen fertilizer impacts on sunflower crop in contrasting environments of Punjab, Pakistan - Wajid Nasim; Ashfaq Ahmad; Asad Amin; Muhammad Tariq; Muhammad Awais; Muhammad Saqib; Khawar Jabran; Ghulam Mustafa Shah; Syeda Refat Sultana; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Muhammad Zaffar Hashmi; et al. (Environmental Science and Pollution Research, 2018)

Sustainable Geological Heritage Development Approach in Sarawak Delta, Sarawak, Malaysia - Dana Badang; Che Aziz Ali; Ibrahim Komoo; Mohd. Shafeea Leman (Geoheritage, 2017)

A New Equation for the Shear Strength of Cable Bolts Incorporating the Energy Balance Theory - Haleh Rasekh; Ali Mirzaghorbanali; Jan Nemcik; Naj Aziz; Xuwei Li (Geotechnical and Geological Engineering, 2017)

The association of urinary interferon-gamma inducible protein-10 (IP10/CXCL10) levels with kidney allograft rejection - Ali Raza; Sadaf Firasat; Shagufta Khaliq; Tahir Aziz; Muhammed Mubarak; Syed Ali Anwar Naqvi; Syed Qasim Mehdi; Syed Adib-ul-Hasan Rizvi; Aiysha Abid (Inflammation Research, 2017)

Insertion sequences enrichment in extreme Red sea brine pool vent - Ali H. A. Elbehery; Ramy K. Aziz; Rania Siam (Extremophiles, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Breast Cancer Knowledge Among Male High School Students in Saudi Arabia - Samia Al-Amoudi; Moaiad Tariq Abdul-Aziz AlHomied; Nasser Youssef Nasser AlSayegh; Osama Naseem Ismail Radi; Mohammed Majed Suliman Zagzoog; Omar Faisal Mubarak Aloufi; Abdullah Abdulkarim Ali Al-Harbi; Safwan Tayeb; Mohammed Hassanien; Mahmoud Al-Ahwal; Basem Eldeek; Steve Harakeh (Journal of Cancer Education, 2016)

Factors Influencing the Quality of Encapsulation in Rock Bolting - Naj Aziz; Peter Craig; Ali Mirzaghorbanali; Jan Nemcik (Rock Mechanics and Rock Engineering, 2016)

Behavior of Fiber Glass Bolts, Rock Bolts and Cable Bolts in Shear - Xuwei Li; Naj Aziz; Ali Mirzaghorbanali; Jan Nemcik (Rock Mechanics and Rock Engineering, 2016)

Tempol and perindopril protect against lipopolysaccharide-induced cognition impairment and amyloidogenesis by modulating brain-derived neurotropic factor, neuroinflammation and oxido-nitrosative stress - Mohammed Ragab Abdel-Aziz Ali; Amira Morad Hussein Abo-Youssef; Basim Anwar Shehata Messiha; Mahmoud Mohamed Khattab (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Health risk assessment of heavy metals and bacterial contamination in drinking water sources: a case study of Malakand Agency, Pakistan - Javed Nawab; Sardar Khan; Sharafat Ali; Hassan Sher; Ziaur Rahman; Kifayatullah Khan; Jianfeng Tang; Aziz Ahmad (Environmental Monitoring and Assessment, 2016)

Evaluating the ameliorative efficacy of Spirulina platensis on spermatogenesis and steroidogenesis in cadmium-intoxicated rats - Mayada R. Farag; R. M. Abd EL-Aziz; H. A. Ali; Sahar A. Ahmed (Environmental Science and Pollution Research, 2016)

Catalytic oxidative desulfurization of diesel oil by Co/Mn/Al2O3 catalysts—tert-butyl hydroperoxide (TBHP) system: preparation, characterization, reaction, and mechanism - Wan Nur Aini Wan Mokhtar; Wan Azelee Wan Abu Bakar; Rusmidah Ali; Abdul Aziz Abdul Kadir (Clean Technologies and Environmental Policy, 2015)

Characterization and selection of walnut (Juglans regia L.) genotypes from seedling origin trees - Abdollah Khadivi-Khub; Aziz Ebrahimi; Ali Mohammadi; Aliakbar Kari (Tree Genetics & Genomes, 2015)

Shoot tip regeneration and optimization of Agrobacterium tumefaciens-mediated transformation of Broccoli (Brassica oleracea var. italica) cv. Green Marvel - Seyed Ali Ravanfar; Maheran Abdul Aziz (Plant Biotechnology Reports, 2015)

Structural and functional effects of early exposure to 4-nonylphenol on gonadal development of Nile tilapia (Oreochromis niloticus): a-histological alterations in ovaries - T. El-Sayed Ali; S. H. Abdel-Aziz; A.-F. M. El-Sayed; S. Zeid (Fish Physiology and Biochemistry, 2014)

Structural and functional effects of early exposure to 4-nonylphenol on gonadal development of Nile tilapia (Oreochromis niloticus): b-histological alterations in testes - T. El-Sayed Ali; S. H. Abdel-Aziz; A.-F. M. El-Sayed; S. Zeid (Fish Physiology and Biochemistry, 2014)

Effects of Shear Rate on Cyclic Loading Shear Behaviour of Rock Joints Under Constant Normal Stiffness Conditions - Ali Mirzaghorbanali; Jan Nemcik; Naj Aziz (Rock Mechanics and Rock Engineering, 2014)

Effects of Cyclic Loading on the Shear Behaviour of Infilled Rock Joints Under Constant Normal Stiffness Conditions - Ali Mirzaghorbanali; Jan Nemcik; Naj Aziz (Rock Mechanics and Rock Engineering, 2014)

An Elasto-Plastic Constitutive Model for Rock Joints Under Cyclic Loading and Constant Normal Stiffness Conditions - Jan Nemcik; Ali Mirzaghorbanali; Naj Aziz (Geotechnical and Geological Engineering, 2014)

Hepatoprotective effect of silyamarin in individuals chronically exposed to hydrogen sulfide; modulating influence of TNF-α cytokine genetic polymorphism - Ali Mandegary; Arastoo Saeedi; Aziz Eftekhari; Vahideh Montazeri; Elham Sharif (DARU Journal of Pharmaceutical Sciences, 2013)

Deterministic and probabilistic seismic hazard analysis for Gwadar City, Pakistan - Shafiq Ur Rehman; Muhammad Khalid; Asif Ali; Abd El-aziz Khairy Abd El-Aal (Arabian Journal of Geosciences, 2013)

Ranging and foraging of Himalayan grey langurs (Semnopithecus ajax) in Machiara National Park, Pakistan - Riaz Aziz Minhas; Usman Ali; Muhammad Siddique Awan; Khawaja Basharat Ahmed; Muhammad Nasim Khan; Naeem Iftikhar Dar; Qamar Zaman Qamar; Hassan Ali; Cyril C. Grueter; Yamato Tsuji (Primates, 2013)

Molecular identification of a novel inulinolytic fungus isolated from and grown on tubers of Helianthus tuberosus and statistical screening of medium components - Samia Abd Allah AbdAl-Aziz; Mohammad Magdy El-Metwally; Wesam Eldin Ismail Ali Saber (World Journal of Microbiology and Biotechnology, 2012)

Erratum to: Haemopoiesis in the head kidney of tilapia, Oreochromis niloticus (Teleostei: Cichlidae): a morphological (optical and ultrastructural) study - El-Saydah H. Abdel-Aziz; Suzan B. S. Abdu; T. El-Sayed Ali; Huda F. Fouad (Fish Physiology and Biochemistry, 2012)

Sexual patterns and protogynous sex reversal in the rusty parrotfish, Scarus ferrugineus (Scaridae): histological and physiological studies - El-Sayedah H. Abdel-Aziz; Fayzah A. Bawazeer; Tamer El-Sayed Ali; Mashael Al-Otaibi (Fish Physiology and Biochemistry, 2012)

Assessment of radiological hazard of NORM in Margalla Hills limestone, Pakistan - Muhammad Ali; Aziz Ahmed Qureshi; Abdul Waheed; Muzahir Ali Baloch; Hamza Qayyum; Muhammad Tufail; Hameed Ahmed Khan (Environmental Monitoring and Assessment, 2012)

Brassinolide alleviates salt stress and increases antioxidant activity of cowpea plants (Vigna sinensis) - Ali Abdel Aziz El-Mashad; Heba Ibrahim Mohamed (Protoplasma, 2012)

Study of heritable variation and genetics of earliness in mungbean (Vigna radiata L. Wilczek) - Aziz ur Rehman; Muhammad Amjad Ali; Muhammad Saleem; W. Tadesse (Euphytica, 2010)

Haemopoiesis in the head kidney of tilapia, Oreochromis niloticus (Teleostei: Cichlidae): a morphological (optical and ultrastructural) study - El-Saydah H. Abdel-Aziz; Suzan B. S. Abdu; Tamer El-Sayed Ali; Huda F. Fouad (Fish Physiology and Biochemistry, 2010)

Ex-situ Bioremediation of Crude Oil in Soil, a Comparative Kinetic Analysis - Leila Mohajeri; Hamidi Abdul Aziz; Mohamed Hasnain Isa; Mohammad Ali Zahed; Soraya Mohajeri (Bulletin of Environmental Contamination and Toxicology, 2010)

Polyhydroxyalkanoate production from anaerobically treated palm oil mill effluent by new bacterial strain Comamonas sp. EB172 - Mohd Rafein Zakaria; Meisam Tabatabaei; Farinazleen Mohamad Ghazali; Suraini Abd-Aziz; Yoshihito Shirai; Mohd Ali Hassan (World Journal of Microbiology and Biotechnology, 2010)

Effect of Initial Oil Concentration and Dispersant on Crude Oil Biodegradation in Contaminated Seawater - Mohammad Ali Zahed; Hamidi Abdul Aziz; Mohamed Hasnain Isa; Leila Mohajeri (Bulletin of Environmental Contamination and Toxicology, 2010)

Cascade Impactor (CI) Mensuration—An Assessment of the Accuracy and Precision of Commercially Available Optical Measurement Systems - Frank Chambers; Aziz Ali; Jolyon Mitchell; Christopher Shelton; Steve Nichols (AAPS PharmSciTech, 2010)

Mucor hiemalis: a new source for uricase production - Mojtaba Tabatabaei Yazdi; Gholamreza Zarrini; Elham Mohit; Mohammad Ali Faramarzi; Neda Setayesh; Navid Sedighi; Farzaneh Aziz Mohseni (World Journal of Microbiology and Biotechnology, 2006)

Microbial production of testosterone and testololactone in the culture of Aspergillus terreus - Mohammad Ali Faramarzi; Mojtaba Tabatabaei Yazdi; Mohsen Amini; Farzaneh Aziz Mohseni; Gholamreza Zarrini; Amir Amani; Abbas Shafiee (World Journal of Microbiology and Biotechnology, 2004)

Characterization and identification of Oya virus, a Simbu serogroup virus of the genus Bunyavirus, isolated from a pig suspected of Nipah virus infection - Y. Kono; Y. Yusnita; A. R. Mohd Ali; M. Maizan; S. H. Sharifah; O. Fauzia; M. Kubo; A. J. Aziz (Archives of Virology, 2002)

The 12th Conference of the Entomological Society of Israel Innovations in Pheromone Research and Application in Israel - M. Wysoki; G. Forer; E. Dunkelblum; Miriam Harel; Polina Fraistat; Devora Gordon; L. Anshelevich; M. Kehat; M. Kehat; L. Anshelevich; Devora Gordon; Miriam Harel; et al. (Phytoparasitica, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)